Pesticide residue profiles, dietary risk assessment, and mitigation strategies in citrus production systems of Pakistan - Muneer Abbas; Akbar Hayat; Sohaib Afzaal; Muhammad Ghayoor Husnain; Hira Tariq; Fiaz Hussain; Niaz Hussain; Muhammad Saleem; Dilbar Hussain; Aleena Alam; Wang Dongze; Sohail Abbas (Food Control, 2026)

Genome sequencing reveals genes under selection for olfactory transduction in highland sheep - Anees Ahmad; Muhammad Ibrahim; Muhammad Yaqoob; Muhammad Fahim; Sher Hayat Khan; Israr Ud Din; Majid Khan; Sohail Ahmad (Molecular Genetics and Genomics, 2026)
Kutta is an indigenous sheep breed found in the mountainous region of Swat, Pakistan. In this study we evaluated the performance of Kutta sheep within their natural habitat and identified genomic regions associated with environmental adaptability using whole genome sequencing. Flocks are mostly managed under a transhumant production system with year-round breeding. Kutta sheep demonstrated higher lambing efficiency under the available resources. Although the body size of rams and ewes was comparable, significant variation was observed among different age groups. Whole genome sequencing identified 15.46 million variants relative to Oar_v1.0 reference genome assembly. Exonic variants accounted for 2.3% of all protein coding gene variants and affected 6347 genes. These genes were primarily enriched in pathways related to G protein-coupled receptor signaling (700 genes) and olfactory transduction (500 genes). Selective sweep analysis detected 1930 genes within the regions of high homozygosity across the genome. Based on homozygosity patterns, biological relevance, and colocalization with known QTLs, 11 candidate genes were identified as putative selective signature. Five of these genes (OR4C6L, OR1086L, OR5AK2L, QR5T2L, OR9Q2) belonged to the olfactory receptor family. These olfactory receptor genes may contribute to high-altitude adaptation in Kutta sheep by enhancing their ability to locate food resources, recognize mates, and detect predators in challenging mountainous environments. Further screening of the OR4C6L sequence across 12 indigenous sheep breeds revealed marked differences between highland and lowland populations. Collectively, these findings provide comprehensive genomic insights into high-altitude adaptation of sheep and highlight the potential role of olfactory perception in survival and environmental fitness.

Precise dual-gene knockout of MSTN and SOCS2 via cytidine base editing enhances muscling and growth in goats - Ling Li; Ming-Xing Cao; Muhammad Farhab; Paing Oo Kyaw; Shu-Qi Zhao; Yi Zhao; Feng-Lei Chen; Tariq Sohail; Ejaz Ahmad; Shao-Xian Cao; Yu-Guo Yuan (Functional & Integrative Genomics, 2026)

Nanoplastics in aquatic ecosystems: Disruptions to fish digestive physiology and gut microbiota - Syed Sikandar Habib; Muhammad Sohail; Francesco Fazio (Marine Pollution Bulletin, 2026)

Leakage-aware depth-blocked evaluation of a hybrid CNN–transformer for continuous calcite concentration prediction from single-well conventional logs - Hafiz Hussain Ahmad; Zhishui Liu; Shi Lei; Song Zhaohui; Shaukat Khan; Sohail Ahmed; Muhammad Junaid; Zhixiu Liu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

How geopolitical risks, green finance, and environmental technologies dynamics shape energy trilemma in BRICS economies? - Muhammad Usman; Yongming Huang; Muhammad Sohail Amjad Makhdum; Daniel Balsalobre-Lorente (Energy Policy, 2026)

Self-powered electrochemical glucose sensing enabled by zirconium holmium oxide/MXene/graphene nanocomposites with integrated energy storage - Nora Mobark Farhan; Saba Khalil; M.S. Al-Buriahi; Muhammad Ali Hamza Shahbaz; Nissren Tamam; Amir Muhammad Afzal; Abhinav Kumar; Sohail Mumtaz (Analytica Chimica Acta, 2026)

Foliar application of Ascorbic acid and Gibberellic acid to enhance salinity tolerance in maize crop (Zea mays) - Hira Fatima; Hummera Nawaz; Ameer Khan; Amina Ameer; Muhammad Nadeem; Sohail Abbas (Cereal Research Communications, 2026)

Artificial intelligence, environmental innovation, and climate-related sustainable development: evidence from BRICS economies - Muhammad Sajid Mehmood; Lu Di; Qian Hongsheng; Ali Sohail; Gang Li; Qin Yaochen (Environment, Development and Sustainability, 2026)

Pesticides-induced histopathological and biochemical alterations in fish: Impacts and restoration strategies - Shariqul Islam; Muhammad Sohail; Md. Fazle Rohani; Shahadat Hossain; S.M. Majharul Islam (Science of The Total Environment, 2026)

Heterojunction interfacial Mo − S bond induced directional electron transport enables efficient visible-light-driven hydrogen evolution - Yidong Pan; Yufeng Fan; Yang Fu; Zhichao Deng; Muhammad Sohail Riaz; Hong Li; Weiju Hao; Jinchen Fan; Guisheng Li; Qingyuan Bi (Chemical Engineering Journal, 2026)

Therapeutic evaluation of myricetin in experimental arthritis: modulation of inflammatory signaling and oxidative stress pathways - Iqra Ijaz; Tasleem Akhtar; Usman aftab; Nadia Naseem; Muhammad Shahzad; Haleema Sohail; Sumetha Yaseen (Inflammopharmacology, 2026)

Molecular mechanisms underlaying fluoride-induced neurotoxicity: interplay of antioxidants and endoplasmic reticulum stress–mediated apoptotic pathways in rats - Ashiru Dahiru; Ismat Nawaz; Syeda Kiran Riaz; Summaya Sohail Chaudry; Muhammad Jadoon Khan; Qingyu Huang; Muhammad Abbas; Syed Ali Musstjab Akber Shah Eqani (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Identification of miR-21-5p and miR-21-3p regulated hub genes and drug repurposing targets in cervical cancer: an integrative computational analysis - Muhammad Bilal Azmi; Rafia Wasi; Arisha Sohail; Uzma Asif (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Factors influencing circular economy adoption in Pakistan’s construction industry - Rai Waqas Azfar; Mohsin Shah; Mughees Aslam; Muhammad Sohail Anwar Malik; Hamza Alam (Environment, Development and Sustainability, 2026)

Eco-friendly tick control using Pakistani bee propolis: Behavioral and acaricidal effects against Rhipicephalus microplus and Hyalomma marginatum - Shahid Nazeer; Shahid Ullah Khan; Shamsheer Khan; Malik Muhammad Sohail Elahi; Syed Ishtiaq Anjum; Khalil ur Rehman; Ruoa Saleh Almahallawi; Amal Abdullah Aboras; Nada Ibrahim Alribdi; Umber Zaman (Veterinary Parasitology, 2026)

Nanoparticles in potato disease management: Applications, mechanisms, and future perspectives for sustainable crop production - Aneeza Ishfaq; Ishrat Bano; Irfan Haidri; Muhammad Shahid; Muhammad Sohail Akram; Muhammad Khubeb Ashfaq; Sabir Hussain; Tanvir Shahzad; Faisal Mahmood (Physiological and Molecular Plant Pathology, 2026)

The role of financial inclusion, social equity, and technological innovation to promote inclusive wealth: Empirical evidence from selected G 20 countries - Sohail Abbas; Shazia Kousar; Farwa Jabbir; Muhammad Afzal; Aena Abid; Heli Lu (Journal of Environmental Management, 2026)

Biochemical and computational characterization of a recombinant catalase from Kocuria rhizophila for degradation of hydrogen peroxide in textile wastewater - Asma Zafar; Hira Mubeen; Sadaf Hameed; Mahjabeen Khan; Hafsa Sohail; Maheen Zaka; Muhammad Nauman Aftab; Anuga Liyanage (Antonie van Leeuwenhoek, 2026)

Immunopharmacological and structural design of a polyprotein based multi epitope vaccine against Powassan virus - Aasia Kalsoom; Syed Hussain Abidi; Sohail Ameer Marwat; Ghulam Shabbir; Muhammad Naveed; Aiman Muhammad Ashraf Mughal; Muhammad Nouman Majeed; Shereen Magdy Korany; Basma Magdy Korany; Khaled Alzhrani; Tariq Aziz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Silver-decorated ZnO nanorods for sunlight-assisted photocatalytic degradation of ciprofloxacin, methyl orange, and 2,4-dinitrophenol in water - Iqra Mazhar; Muhammad Afzaal; Muhammad Altaf; Manzar Sohail; Raja Shahid Ashraf; Abdul-Sattar Nizami (Nanotechnology for Environmental Engineering, 2026)

Enhanced estimation of total organic carbon in the longmaxi shale formation using supervised machine learning with lithofacies characterization via K-means clustering - Shaukat Khan; Zhishui Liu; Zhiqiang Lu; Wakeel Hussain; Sohail Ahmed; Muhammad Sajid; Hafiz Hussain Ahmad; Obaidullah; Imdadullah (Carbonates and Evaporites, 2026)

Sustainable Laccase Production by Anoxybacteroides rupiense UE27 Using Desmostachya bipinnata Biomass: Optimisation and Application in Textile Effluent Treatment - Haniah Saeed; Bushra Rehman; Uroosa Ejaz; Maria Muhammad Ashraf; Amal Siraj; Areesha Mustafa; Muhammad Sohail (Environmental Microbiology, 2026)
Laccase has been widely reported for the detoxification of industrial effluents, yet large‐scale applications require cost‐effective production. This study utilised an innovative approach by employing biomass from the halophyte Desmostachya bipinnata, which has not been previously reported for microbial enzyme production. A newly discovered bacterial species, Anoxybacteroides rupiense, was used for laccase production. Initially, the factors impacting laccase production by the thermophilic strain of A. rupiense UE27 (Genome Project JBHLFH010000000.1) were screened for their significant effects using the Plackett–Burman design. Consequently, Response Surface methodology was adopted to optimise the significant factors, resulting in a maximum laccase yield of 51.69 U L −1 at pH 6.39 and in presence of 0.59 mM CuSO 4 , representing a 4.29‐fold increase compared to the unoptimised conditions. AFM revealed comminution in the plant biomass and FTIR analysis confirmed laccase‐mediated lignin degradation in D. bipinnata biomass, evidenced by shifts in aromatic CC (1597–1650 cm −1 ), CH methyl (2850–2918 cm −1 ) and phenolic OH (3300–3400 cm −1 ) regions. Moreover, growth of A. rupiense UE27 in the presence of textile effluent resulted in 70.6% decolourisation with the subsequent laccase production. Hence, this study presents a sustainable and innovative approach for developing wild biomass‐based processes for the cost‐effective production of laccase by thermophilic bacteria.

Genetic basis of breed variation: Genome wide selection signature of neighboring sheep breeds - Muhammad Ibrahim; Muhammad Yaqoob; Mehmood Alam Khan; Irfan Ullah Wazir; Meshari Mohsen Alwazae; Sohail Ahmad (Small Ruminant Research, 2026)

Dichlorvos toxicity on hemato-biochemical, histopathological, and behavioral parameters in the grass carp (Ctenopharyngodon idella) - Mehvish Saleem; Cristiana Roberta Multisanti; Sana Ullah; Wardah Fazal; Muhammad Sohail; Muhammad Bilal; Muhammad Kashif Ashraf; Caterina Faggio (Ecotoxicology, 2026)

Petrographic and geomechanical evaluation of nikanai ghar formation (KPK) and kuldana formation (Punjab) rocks: A comparative study for their suitability as building materials in Pakistan - Hassan Ayaz; Jiancong Xu; Sohail Ahmad; Muhammad Usama Aslam (Arabian Journal of Geosciences, 2026)

Chemical contaminants and fish: implications for health and ecosystem sustainability - Muhammad Sohail; Mohammad Ali Nematollahi; Sardar Suleman; Syed Sikandar Habib (Environmental Monitoring and Assessment, 2026)

CRISPR-Cas9 and next-generation gene editing strategies for therapeutic intervention of neurodegenerative pathways in Alzheimer’s disease: a state-of-the-art review - Muhammad Sohail Khan; Imran Zafar; Adil Jamal; Fayez Saeed Bahwerth; Samiullah Khan; Muhammad Faizan; Hanif Khan; Muhammad Noman; Kendrix Okeibunor; Ashfaq Ahmad; Muhammad Zain Ul Abedin (Acta Neurologica Belgica, 2026)

Root inoculation with Trichoderma harzianum primes metabolic and stress-response pathways underlying growth and resistance in Brassica rapa - Bilal Ahmad; Aleena Alam; Sohail Abbas; Muhammad Ameer Hamza; Khalid Ali Khan; Hamed A. Ghramh; Raul Narciso C. Guedes; Qiyun Li; Rizhao Chen (Pesticide Biochemistry and Physiology, 2026)

Green-synthesized nanoparticles used to restore soil health and reprogram plant resilience - Babar Iqbal; Inamullah; Amir Abdullah Khan; Ali Raza Khan; Rasheed Akbar; Muhammad Sohail Memon; Guanlin Li; Daolin Du (Journal of Environmental Chemical Engineering, 2026)

Retraction notice to ‘A facile two-step hydrothermal preparation of 2D/2D heterostructure of Bi2WO6/WS2 for the efficient photodegradation of blue under sunlight’ [Environ. Res. 234 (2023) 116550] - Muhammad Fiaz; Manzar Sohail; Ayman Nafady; Geoffrey Will; Md A. Wahab (Environmental Research, 2026)

Improving Wheat Production in Pakistan Through an Economically Viable Solar‐Powered Rain Gun Sprinkler Irrigation System - Muhammad Asif; Shahzad Hussain Dahri; Bashir Ahmad; Noman Latif Sadozai; Sohail Raza Haidree; Abdul Hannan; Syed Qasim Ali Naqvi (Irrigation and Drainage, 2026)
In rainfed agriculture, limited water availability has become a challenging factor for sustainable farming and economic security. For regions with variable climate conditions, efficient water management practices must be adopted to improve livelihoods and food security. This study aimed to evaluate the role of supplemental irrigation for wheat crops in the Pothwar region. The irrigation management consists of I 0 (rainfed), I 1 (10 mm presowing), I 2 (10 mm at 50% soil moisture depletion [SMD]) and I 3 (25 mm at 75% SMD). The results revealed that, under I 3 , the grain yield increased by 49% and 17%, followed by I 2 (47% and 12%) compared to the rainfed yield of 1.85 and 3.93 tons/ha in Jand and NARC, respectively. The analysis of variance and Tukey's honestly significant difference (HSD) test revealed that the yield for I 0 value was significantly lower than that of all the irrigation treatments, while there were no significant differences among I 1 , I 2 and I 3 . The net benefit analysis revealed that I 3 was an economic irrigation schedule and paid back the total intervention cost by generating PKR 389,915/ha at NARC and PKR 283,915/ha at Jand in 3.83 and 4.93 years, respectively. This viable economic return makes solar‐powered irrigation systems reliable sources of water for water‐scarce and climate‐variable regions.

Retraction notice to ‘Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward’ [Chemosphere 325 (2023) 138367] - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2026)

Interactive effects of incubation and post-hatch lighting schedules on blood biochemistry and meat quality characteristics in Japanese quail - Hussnain Ali Akram; Jibran Hussain; Sohail Ahmad; Muhammad Hayat Jaspal (Tropical Animal Health and Production, 2026)

Hematological, Histological, and NMR Analysis of Meat Quality and Growth Performance of Broilers Fed with Probiotics Bacillus licheniformis-Supplemented Poultry Feed - Basit Ali Khan; Sundas Sharif; Amna Mehdi; Iram Liaqat; Sikander Ali; Asad-ur-Rehman; Liangcai Peng; Sohail Afzal; Muhammad Nauman Aftab (Probiotics and Antimicrobial Proteins, 2026)

Integrative analysis of rhizosphere metabolomics and root anatomical adaptations in wheat under drought stress: comparative insights from DH-11 and PK-13 - Sohail Ahmed; Muhammad Kaleem Samma; Faisal Mehdi; Kamran Yaqoub; Manzer H. Siddiqui; Amna Jabbar Siddiqui; Syed Ghulam Musharraf; Saddia Galani; Zubia Rashid; Hania Ahmed (Physiology and Molecular Biology of Plants, 2026)

Coprinellus gregariodiguttulatus , a New Coprinoid Species from Margalla Hills, Islamabad, Pakistan - Fahim Ullah; Malka Saba; Iram Fatima; Muhammad Asif; Mohsin Ullah; Fazli Maula; Wajahat Akram; Amir Sohail (New Zealand Journal of Botany, 2026)
Coprinellus gregariodiguttulatus is described as a new species from Quaid‐i‐Azam University, Islamabad, Pakistan, based on morphological and molecular analyses. The species is distinguished by its small gray to light gray basidiomata, paraboloid to hemispherical pileus, and oblong to obovoid or rarely lemon basidiospores. Phylogenetic analysis of the internal transcribed spacer (ITS) region supports its placement within Coprinellus sect. Disseminati is a distinct lineage, closely related to but separate from other known taxa. This discovery from an underexplored region highlights the potential for uncovering further novel fungal diversity in Pakistan.

Sublethal effects of azadirachtin on life table parameters of Musca domestica (Diptera: Muscidae): implications for population dynamics in Pakistan - Naeem Iqbal; Nauman Sadiq; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Muhammad Nadir Naqqash; Adnan Akhter (International Journal of Tropical Insect Science, 2026)

Covalent triazine frameworks: Synthesis strategies, physicochemical properties, and advanced sustainable energy applications - Hamid Ali; Basem Al Alwan; Atef El Jery; Asma M. Alenad; Abdellatif M. Sadeq; Muhammad Sohail (Desalination, 2026)

Porphyrin/metalloporphyrin and their conjugates: a promising platform for drug delivery - Dure Najaf Iqbal; Sohail Khaliq; Muhammad Zaeem Mehdi; Mohammed H. AL Mughram; Mahmood Ahmed (Molecular Diversity, 2026)

Correction: Modeling soil moisture and evapotranspiration dynamics from variably irrigated vegetable fields - Mulatu Liyew Berihun; Girma Worku Awoke; Fitsum Tilahun Teshome; Niguss Solomon Hailegnaw; Tewodros T. Assefa; Muhammad Sohail Waqas; Haimanote K. Bayabil (Modeling Earth Systems and Environment, 2026)

Modeling soil moisture and evapotranspiration dynamics from variably irrigated vegetable fields - Mulatu Liyew Berihun; Girma Worku Awoke; Fitsum Tilahun Teshome; Niguss Solomon Hailegnaw; Tewodros T. Assefa; Muhammad Sohail Waqas; Haimanote K. Bayabil (Modeling Earth Systems and Environment, 2026)

Correlation of high pollen concentrations with air pollutants and meteorological parameters: “the case of Islamabad, Pakistan” - Muhammad Humayun; Kalim Ullah; Saadia Naseem; Sohail Baber; Nighat Akbar; Zahid Ali (International Journal of Biometeorology, 2026)

Geographic distribution patterns, population dynamics, and habitat vulnerability of endangered and endemic Trillium govanianum - Syed Waseem Gillani; Mushtaq Ahmad; Muhammad Manzoor; Muhammad Waheed; Raja Waqar Ahmed Khan; Amir Sohail (Environmental Monitoring and Assessment, 2026)

Status of insecticide resistance in Spodoptera litura (Lepidoptera: Noctuidae) on cauliflower, Punjab, Pakistan - Dilbar Hussain; Muhammad Sohail Qadir; Muhammad Asrar; Muhammad Saleem; Usama Saleem; Zeeshan Javed; Kanwal Hanif; Arshed Makhdoom Sabir; Ijaz Haider; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal (International Journal of Tropical Insect Science, 2026)

Southward to northward shifting trends of monsoonal precipitation and their connections with atmospheric circulations over Pakistan: A comparative study of 1961–1990 and 1991–2020 - Sohail Abbas; Amina Ameer; Fenglin Lv; Tingting Li; Yi Chen; Liang Cao; Heli Lu; Yasir Latif; Muhammad Yaseen; Siqi Lu; Wanfu Feng; Amjad Ali Khan (Journal of Hydrology, 2026)

Synergistic Ni single-atom–nanoparticle interfaces for poison-resistant CO₂ electroreduction - Syed Shoaib Ahmad Shah; Jamal Kazmi; Muhammad Altaf Nazir; Manzar Sohail; Muhammad Sufyan Javed; Tayyaba Najam; Lishan Peng; Ramón A. Alvarez-Puebla (Chemical Engineering Journal, 2026)

Synergistic Sustainable Strategies for Microplastic Pollution Eradication by Hedgehog − Shaped Polyoxometalate − Ionic Liquids Supported Magnetic Biochar - Hameed Ullah; Tahani Rahil Aldhafeeri; Inas A. Ahmed; Khurram Shahzad Munawar; Shahid Hussain; Nadeem Nawaz; Uzma Saleem; Muhammad Sohail; Hafiz Muhammad Asif (Water, Air, & Soil Pollution, 2025)

Molecular Insights into Interactions between Ofloxacin and Ionic Micelles - Saqib Rabbani; Areesha Maryam; Muhammad Sohail; Athar Yaseen Khan (The Journal of Membrane Biology, 2025)

Optimizing tree crown density of finite coastal vegetation patches for enhanced tsunami mitigation - Fakhar Muhammad Abbas; Ali Abdullah Zaid Aldrees; Sohail Iqbal; Amina; Muhammad Atiq Ur Rehman Tariq; Naveed Anjum; Mujahid Iqbal; Usman Ghani; Ghufran Ahmed Pasha (Natural Hazards, 2025)

Morpho-palynological evaluation of family Poaceae from arid and semi-arid regions of Pakistan - Bibi Sadia; Mushtaq Ahmad; Wajia Noor; Syed Waseem Gillani; Muhammad Manzoor; Zhiduan Chen; Lixin Zhang; Shazia Sultana; Amir Sohail (Genetic Resources and Crop Evolution, 2025)

Whole-Genome analysis of Bacillus subtilis MBBL2 genomic characterization and comparative genomics - Hajra Sohail; Muhammad Naveed; Tariq Aziz; Rania Ali El Hadi Mohamed; Fakhria A. Al-Joufi (Functional & Integrative Genomics, 2025)

Drought mitigation and livelihood improvement options through rainwater harvesting structures in a rainfed agricultural system - Muhammad Sohail Waqas; Haimanote K. Bayabil; Niguss Solomon Hailegnaw; Saddam Hussain; Aqil Tariq; Saqib Abubakar (Agricultural Systems, 2025)

Recent advances in conducting polymers for hybrid solar-driven evaporation systems: Fundamentals, innovations, and applications - Bushra Shakoor; Muhammad Sultan Irshad; Uzma Ghazanfar; Humaira Razzaq; Naila Arshad; Ghazala Maqsood; Iftikhar Ahmed; Muhammad Atif Ali; Muhammad Sohail Asghar; Irshad Hussain; Tao Mei; Tran Vinh Dieu; et al. (Chemical Engineering Journal, 2025)

NiMn-LDH/polypyrrole photothermal structures for interfacial solar steam generation - Ghazala Maqsood; Muhammad Sohail Asghar; Bushra Shakoor; Muneerah Alomar; Muhammad Atif Ali; Yi E; Tao Mei; Muhammad Sultan Irshad; Xianbao Wang (Chemical Engineering Journal, 2025)

Ultraviolet assisted defects engineering of metal organic frameworks towards high performance oxygen evolution reaction - Rana Sami Ul Haq; Zhihao Lei; Shuai Qi; Muhammad Ibrar Ahmed; Vibin Perumalsamy; Yitong Cao; Kavitha Ramadass; Binodhya Wijerathne; Xun Geng; Sohail Ahmed; Long Hu; Liang Qiao; et al. (Chemical Engineering Journal, 2025)

Simulation-based assessment of the impact of conservation tillage and strip intercropping on soil microbial biomass carbon - Sana ur Rehman; Xiaoping Xin; Shahzada Sohail Ijaz; Shroz Fatima; Ayesha Siddiqa; Hayder Bin Khalid; Imran Haider; Rashid Iqbal; Aqib Mahmood; Sajad Hussain; Atta Mohi Ud Din; Taqi Raza; et al. (CATENA, 2025)

Nanogel-based delivery of dequalinium chloride: A novel approach for antimicrobial and controlled drug release - Ammara Sayyeda; Zulcaif Ahmad; Syeda Momna Ishtiaq; Asma Irshad; Saniia Shchinar; Muhammad Farhan Sohail (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Diversity of arthropods fauna in correlation to abiotic factors in wheat crop - Dilbar Hussain; Bushra Khalid; Muhammad Asrar; Usama Saleem; Wafa Abdullah Hamad Alkherb; Muhammad Saleem; Hina Anwar; Saddam Hussain; Muhammad Sohail Qadir; Mubshar Saleem; Khalid Ali Khan; Hamed A. Ghramh; et al. (International Journal of Tropical Insect Science, 2025)

Risk assessment of synthetic insecticides and botanicals to Western honey bee, Apis mellifera (Hymenoptera: Apidae) - Sami Ullah; Naeem Iqbal; Muhammad Sohail Shahzad; Hafiz Azhar Ali Khan; Khalid Rafiq; Allah Ditta Abid; Mudssar Ali; Shafqat Saeed (International Journal of Tropical Insect Science, 2025)

Efficient and sustainable transfer hydrogenation and N-formylation of nitroarenes using a facilely synthesized Co₄N/NC nanocatalyst - Anosha Rubab; Md A. Wahab; Ahmed Abdala; Muhammad Sharif; Waqas Ahmed; Manzar Sohail (Journal of Environmental Chemical Engineering, 2025)

A double-edged sword? Exploring the heterogeneous effects of industrialization, energy efficiency, and disaggregated financial development on environmental management - Zhou Li; Muhammad Usman; Muhammad Sohail Amjad Makhdum; Abdulrahman Alomair (Journal of Environmental Management, 2025)

An effective bi-functional electrocatalyst for electrochemical water splitting using NiCo2O4 nanoparticles decorated with Polypyrrole nanocomposite - Khadija-Tul-Kubra; Faiqa Noreen; Ali Junaid; Atif Nazir; Sehrish Arshad; Komal Bibi; Ayesha Batool; Aleeza Sattar; Aboud Ahmed Awadh Bahajjaj; Sohail Ahmad; Muhammad Shuaib Khand; Syed Imran Abbas Shah (Fuel, 2025)

Bimetallic metal-organic frameworks as versatile electrocatalysts for water splitting in neutral and alkaline environments - Syed Arfan Haider; Tehseen Mushtaq; Bakhtawar Sajjad; Munazza Shahid; Muhammad Altaf; Ayman Nafady; Ghayoor Abbas Chotana; Manzar Sohail; Shahid Rasul; Raja Shahid Ashraf (Fuel, 2025)

Comparative Effects of Antibiotic and Antimicrobial Peptide on Growth Performance, Gut Morphology, Intestinal Lesion Score, Ileal Microbial Counts, and Immune Status in Broilers Challenged with Necrotic Enteritis - Muhammad Muneeb; Ehsaan Ullah Khan; Mubashar Ali; Muhammad Naveed Ul Haque; Muhammad Umar Zafar Khan; Sohail Ahmad (Probiotics and Antimicrobial Proteins, 2025)

Mechanistic insights into lead uptake and immobilization mediated by soybean biochar and arbuscular mycorrhizal fungi in Bidens parviflora - Sadam Khan; Irfan Ullah Shah Syed; Muhammad Riaz; Muhammad Tariq; Tahir shah; Sidra Sohail; Muhammad Imtiaz; Shoaib Akhtar; Jiang Yuanren; Munib Ahmad; Yurong Yang; Hanzhong Jia (Applied Soil Ecology, 2025)

Effect of Bioactive Peptides and Encapsulated Butyric Acid on Growth Performance, Gut Health, Immune Status and Nutrient Digestibility in Broiler Chickens - Mohammad Ahmad Qazi; Ehsaan Ullah Khan; Saima Naveed; Shahid Mehmood; Muhammad Muneeb; Muhammad Talha; Muhammad Shabir Shaheen; Sohail Ahmad (International Journal of Peptide Research and Therapeutics, 2025)

Selenium mitigates boron toxicity in Nicotiana tabacum via altering root anatomy, accumulation of boron, biochemical and physiological aspects - Ghulam Murtaza; Zeeshan Ahmed; Gang Deng; Sohail Akhtar; Muhammad Rizwan; Muhammad Usman; Mona S. Alwahibi; Humaira Rizwana; Tolga İzgü; Özhan Şimşek; Rashid Iqbal; Faisal Zulfiqar (Plant Biosystems, 2025)

Retraction notice to “Template-based textural modifications of polymeric graphitic carbon nitrides towards waste water treatment” [Chemosphere 302, September 2022,134792] - Umair Azhar; Muhammad Sohail Bashir; Muhammad Babar; Muhammad Arif; Afaq Hassan; Asim Riaz; Rana Mujahid; Muhammad Sagir; Saadat Ullah Khan Suri; Pau Loke Show; Jo-Shu Chang; Kuan Shiong Khoo; et al. (Chemosphere, 2025)

Effects of bacteriophage supplementation on performance, gut health and blood biochemistry in broilers challenged with necrotic enteritis - Muhammad Muneeb; Ehsaan Ullah Khan; Saima; Muhammad Suleman; Mian Muhammad Awais; Sohail Ahmad (Research in Veterinary Science, 2025)

Microplastics and nanoplastics across the food web: Challenges and mitigation strategies in securing human health - Mingjun Chen; Ali Raza Khan; Muhammad Sohail Memon; Babar Iqbal (Process Safety and Environmental Protection, 2025)

Spatial distribution of mangrove soil organic carbon in Indus Delta, Pakistan: A multi-sensor remote sensing and machine learning approach - Hammad Gilani; Muddasir Shah; Shahzada Sohail Ijaz; Muhammad Asif; Abid Nazir; Niall P. Hanan (Estuarine, Coastal and Shelf Science, 2025)

Effects of Planting Date and Genotype on Potato Growth and Yield Determination in a Sub-Tropical Continental Growing Environment - Muhammad Sohail Khan; Gerrit Hoogenboom; Syeda Mehwish Gillani; Alam Syed Shah; Ilham Khan (Potato Research, 2025)

Retraction Note to: Anthocyanins Improve Hippocampus-Dependent Memory Function and Prevent Neurodegeneration via JNK/Akt/GSK3β Signaling in LPS-Treated Adult Mice - Muhammad Sohail Khan; Tahir Ali; Min Woo Kim; Myeung Hoon Jo; Jong Il Chung; Myeong Ok Kim (Molecular Neurobiology, 2025)

Foliar-Application of Proline Mitigates Salinity Stress in Two Maize (Zea mays L.) Genotypes: A Comparative Study of Growth, Physiology, Chlorophyll Fluorescence, and Ionic Composition - Tayyaba Naz; Muhammad Mazhar Iqbal; Iftikhar Ahmad; Muhammad Adnan Sohail; Shazia Iqbal; Aftab Jamal; Luis Alfonso Rodriguez-Paez; Marcelo F. Pompelli (Journal of Plant Growth Regulation, 2025)

Microbial transformation: the role of fermentation in advancing nutritional quality and human health - Babar Iqbal; Khulood Fahad Alabbosh; Abdulkareem Raheem; Inam Ullah; Ali Raza Khan; Muhammad Sohail Memon (Archives of Microbiology, 2025)

Functionalized carbon nanotubes interconnected with metal-organic frameworks for in-situ solar-driven evaporation and salt recovery from seawater - Muhammad Sohail Asghar; Muhammad Sultan Irshad; Naila Arshad; Maryam Al Huwayz; Muneerah Alomar; Ghazala Maqsood; Muhammad Atif Ali; Uzma Ghanzanfar; Muhammad Sabir; Jinhua Li; Van-Duong Dao; Nang Xuan Ho; et al. (Water Research, 2025)

How do digital government, circular economy, and environmental regulatory stringency affect renewable energy production? - Ilhan Ozturk; Sana Ullah; Sidra Sohail; Muhammad Tayyab Sohail (Energy Policy, 2025)

Beyond Data, Towards Sustainability: a Sydney Case Study On Urban Digital Twins - Ammar Sohail; Bojie Shen; Muhammad Aamir Cheema; Mohammed Eunus Ali; Anwaar Ulhaq; Muhammad Ali Babar; Asama Qureshi (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2025)
As urban areas grapple with unprecedented challenges stemming from population growth and climate change, the emergence of urban digital twins offers a promising solution. This paper presents a case study focusing on Sydney’s urban digital twin, a virtual replica integrating diverse real-time and historical data, including weather, crime, emissions, and traffic. Through visualization and data analysis techniques, the study explores some applications of this digital twin in urban sustainability, such as spatial ranking of suburbs and automatic identification of correlations between variables. Additionally, the research delves into predictive modeling, employing machine learning to forecast traffic crash risks using environmental data, showcasing the potential for proactive interventions. The contributions of this work lie in the comprehensive exploration of a city-scale digital twin for sustainable urban planning, offering a multifaceted approach to data-driven decision-making

Evaluation of entomopathogenic fungi and nematode species for eco-friendly management of fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) - Usama Saleem; Muhammad Asrar; Dilbar Hussain; Faisal Hafeez; Muhammad Sohail Qadir (International Journal of Tropical Insect Science, 2025)

High-performance PVC/polyacrylate-graphene oxide membranes for Pb (II) and Hg (II) ion removal from polluted water: synthesis, characterization, and adsorption studies - Noreen Nasir; Junaid Raza; Abdul Hamid; Naseem Ahmad Khan; Mubushar Majeed; Muhammad Sohail Aslam; Anis Ali Shah; Muhammad Iftikhar; Bilal Arshad; Muhammad Sohail; Muhammad Saeed; Shifa Shaffique; et al. (Environmental Monitoring and Assessment, 2025)

New insights on the potentiality of deep learning techniques in supporting the assessment of some biotic diseases on maize - Sajjad Hussain Qureshi; Sohail Raza Chohan; Muhammad Usman; Muhammad Luqman; Mueen Alam Khan; Baber Ali; Reem M. Aljowaie; Mohamed S. Elshikh; Rashid Iqbal (Journal of Plant Pathology, 2025)

Adaptive divergence in Ostrinia furnacalis: Diet-based fitness specification across wild, domestic and hybrid populations - Aleena Alam; Sohail Abbas; Faisal Hafeez; Muhammad Shakeel; Arzlan Abbas; Khalid Ali Khan; Hamed A. Ghramh; Jamin Ali; Adil Tonğa; Rizhao Chen (Crop Protection, 2025)

Distribution modelling and future prediction of a threatened species - Heracleum candicans Wall. ex DC.; Within the framework of biotic and abiotic interactions - Jawad Hussain; Shujaul Mulk Khan; Muhammad Shakeel Khan; Zafeer Saqib; Abdullah; Zeeshan Ahmad; Maria Shah; Nazir Mohammad; Zareena Batool; Amir Sohail; Jie Liu (Journal of Environmental Management, 2025)

Marine life as a source of anti-prostate cancer agents: an updated overview (2003–2023) - Amjad Hussain; Ammara Sohail; Muhammad Sajid Hamid Akash; Sarosh Iqbal; Kanwal Rehman; Muhammad Imran; Shoaib Khan; Muhammad Adnan Ayub; Daijie Wang; Dildar Ahmed; Mohammed Hadi Ali Al-Jumaili; Maria Bashir; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Carbapenem Resistant Serratia marcescens Harboring blaOXA-48, armA and aac(6′)-Ib-cr Genes: The First Baseline Study from Pakistan - Amna Kausar; Muhammad Sohail; Mohsin Khurshid; Hafiz Ghulam Murtaza Saleem (Current Microbiology, 2025)

Remediation of microplastics-contaminated agricultural soils by unmodified and modified biochar derived from Solidago canadensis L. - Babar Iqbal; Muhammad Junaid Nazir; Jiabao Lou; Yanjiao Wang; Eun Hea Jho; Mao Ye; Mingming Sun; Abdulkareem Raheem; Inamullah; Muhammad Sohail Memon; Guanlin Li; Xin Zhao; et al. (Process Safety and Environmental Protection, 2025)

Bending performance of a novel geopolymer non-dismantling sandwich insulation formwork: Experimental, theoretical, and numerical simulation - Shuang Li; Muhammad Sohail Saleh; Jianjun Zhao; Haoran Wang; Haopeng Liu; Muhammad Saeed Iqbal (Engineering Structures, 2025)

Zinc Biofortification in Cereal Crops: Overview and Prospects - Muhammad Fraz Ali; Lijuan Ma; Sidra Sohail; Usman Zulfiqar; Tajamul Hussain; Xiang Lin; Dong Wang (Journal of Soil Science and Plant Nutrition, 2025)

Combined Impact of Waste Water and Farm Yard Manure on Growth of Tomato (Solanum lycopersicum L.) and Soil Health: A Sustainable Agriculture Approach - Arsalan Saghir; Muhammad Sohail Akram; Shahzad Ali; Shahla Rashid; Muhammad Ajmal Farhad; Hafiz Muhammad Tayyab Khan; Syed Ayyaz javed; Mohammad Raish; Muhammad Khubaib (Journal of Soil Science and Plant Nutrition, 2025)

Correction: Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Physicochemical, Enzymatic, and Microbial Responses to Phosphofructokinase Overexpressing Transgenic Potato Cultivation: A Pot Experiment - Muhammad Junaid Sadiq Gill; Umer Ali; Aqib Hassan Ali Khan; Ismat Nawaz; Tayyab Ashfaq Butt; Cyrus Raza Mirza; Ameena Iqbal; Arfan Ali; Faiz Ur Rahman; Sohail Yousaf; Mazhar Iqbal (American Journal of Potato Research, 2025)

CO2 capture using mixed amines: experimental DFT investigation with focus on improvements in cyclic efficiency and NO interference - Muhammad Haris; Arif Aziz; Muhammad Sohail; Waseem Sardar (Environmental Science and Pollution Research, 2025)

Shaping sustainable tourism: the influence of norms and social media rumors on tourist behavior - Muhammad Kashif Javed; Muhammad Sohail Tahir; Antonio Capaldo; Jamil Ahmad; Allah Wasaya; Affan Uddin Ahmed; Muhammad Irfan Chani (Environment, Development and Sustainability, 2025)

Challenges and outlooks for the polyoxometalates, metal-organic frameworks (POMs-MOFs) hybrid materials in water treatment technologies - Ghulam Murtaza; Muhammad Ibrar Ahmed; Kewei Yu; Xingda An; Syed Shoaib Ahmad Shah; Manzar Sohail (Environmental Research, 2025)

Effects of replacing antibiotics with probiotics and antimicrobial peptides on performance, gut health, carcass traits, meat quality, and welfare in broilers infected with Eimeria and Clostridium perfringens - Muhammad Muneeb; Ehsaan Ullah Khan; Mubashar Ali; Muhammad Suleman; Muhammad Shabir Shaheen; Muhammad Shahbaz Zafar; Sohail Ahmad (Tropical Animal Health and Production, 2025)

Synthesis, hydrolysis, and COX-2/15-LOX inhibitory evaluation of 4-Acetamidophenyl 4-Bromobenzoates - Uzma Afzal; Abid Mahmood; Muhammad Zubair; Nasir Rasool; Aqsa Kanwal; Maria Sohail; Gulraiz Ahmad (Medicinal Chemistry Research, 2025)

Ethylene precursor, 1-amino cyclopropane-1-carboxylic acid, induced distinct morpho-physio-biochemical improvements to cadmium-stressed mungbean (Vigna radiata L.) - Aneeqa Munawar; Muhammad Tariq Javed; Nudrat Aisha Akram; Sadia Zafar; Muhammad Sohail Akram (South African Journal of Botany, 2025)

Heavy Metal Uptake by Spirogyra splendida and Spirogyra circumlineata: A Sustainable Approach to Industrial Wastewater Remediation - Sadam Khan; Yuanren Jiang; Siqi Shen; Muhammad Riaz; Muhammad Tariq; Zhenxin Li; Rafiq Ahmad; Sidra Sohail; Nazim Hassan (Water, Air, & Soil Pollution, 2025)

CFD analysis of flow dynamics around the series of dikes with alternative length layout - Rizwan Haider; Sohail Iqbal; Fakhar Muhammad Abbas; Amina Fakhar (Natural Hazards, 2025)

Tabrizicola caldifontis sp. nov., Isolated from Hot Spring Sediment Sample - Neeli Habib; Inam Ullah Khan; Muhammad Saqib; Mohammad Saeid Hejazi; Vahideh Tarhriz; Sohail Ahmad Jan; Cynthia Meza; Aparna Banerjee; Manik Prabhu Narsing Rao; Wen-Jun Li (Current Microbiology, 2025)

Application of gamma spectrum analysis techniques for natural radioactivity measurements using NaI(Tl) detector - Namra Naeem; Muhammad Sohail; Rizwan Ahmed; Shoaib Masood (Environmental Monitoring and Assessment, 2025)

Designing of efficient CoLa2O4/V-Ag-MOF hybrid electrode for energy storage, hydrogen evolution reaction, and chemical sensors - Asad Ur Rehman; Nimra Muzaffar; Imad Barsoum; Amir Muhammad Afzal; Muhammad Ali; Muhammad Waqas Iqbal; Zubair Ahmad; Sohail Mumtaz; Aboud Ahmed Awadh Bahajjaj; Shaik Abdul Munnaf (Fuel, 2025)

Burkholderia sp. AQ12-mediated Molecular Adjustments Assist Growth of Salt-stressed Cotton (Gossypium hirsutum L.) By Modulating Biochemical Status and Nutrient Acquisition Patterns - Sidra Batool; Sijal Fatima; Uzma Qaisar; Muhammad Shahid; Muhammad Sohail Akram (Journal of Soil Science and Plant Nutrition, 2025)

Impacts of Conservation Tillage on Agricultural Land Development: A Review - Xue Liang; Sana Ur Rehman; Wang Zhiqi; Muhammad Ali Raza; Imran Haider; Muhammad Hayder Bin Khalid; Amjad Saeed; Zafar Iqbal; Shroz Fatima; Ayesha Siddiqa; Muhammad Ansar; Shahzada Sohail Ijaz; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Assessing the Influence of Potassium Fertilizer Variations on Growth, Yield, and Crop Quality of Sugarcane (Saccharum officinarum L.) Genotypes - Wajid Ali Hisbani; Bonface O. Manono; Muhammad Nawaz; Kashf Mehmood; Zuhair Hasnain; Afroz Rais; Sohail Irshad; Danish Ibrar; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (International Journal of Plant Production, 2025)

Novel mutations in exon 2 of follistatin (FST) gene associated with wool fiber diameter in sheep - Tahira Mir; Muhammad Ibrahim; Muhammad Siraj; Sajid Ali Khan Bangash; Sher Hayat Khan; Majid Khan; Muhammad Tayyab; Sohail Ahmad (Small Ruminant Research, 2025)

Postharvest melatonin application attenuates browning, delays softening, and maintains the antioxidant potential of jackfruit bulbs - Jashanpreet Kaur; Zora Singh; Muhammad Sohail Mazhar; Hafiz Muhammad Shoaib Shah; Eben Afrifa-Yamoah; Andrew Woodward (Food Chemistry, 2025)

Integration of physio-biological methods for remediation of dyes and toxic metals from textile wastewater - Muhammad Ayaz; Aqib Hassan Ali Khan; Kang Song; Asmat Ali; Sohail Yousaf; Abeer Kazmi; Abdur Rashid (Bioresource Technology Reports, 2025)

Cooling load reduction strategies for community worship place towards attaining sustainability: a life cycle cost perspective - Fatima Anwar; Muhammad Sohail Anwar Malik; Mughees Aslam; Rai Waqas Azfar Khan (The International Journal of Life Cycle Assessment, 2025)

Unraveling insect feeding patterns and their ecological impacts on plant defense mechanisms - Arzlan Abbas; Muhammad Zulqar Nain Dara; Farman Ullah; Babu Saddam; Sohail Abbas; Aleena Alam; Mobeen Babar; Faisal Hafeez; Muhammad Dildar Gogi; Hamed A. Ghramh; Khalid Ali Khan; Yasir Niaz; et al. (Journal of Plant Diseases and Protection, 2025)

Evaluation of Genotype × Environment Interaction and Yield Stability of Cotton (Gossypium hirsutum L) Genotypes Under Heat Stress Conditions - Iram Sharif; Saba Aleem; Jamshaid Ali Junaid; Muqadas Aleem; Khazina Jamshaid; Huma Saleem; Muhammad Rizwan; Shahid Munir Chohan; Saqib Sohail; Saba Akram; Muhammad Zeeshan; Ghulam Sarwar (Journal of Crop Health, 2025)

Investigation on radioisotopes evolution in the fuel of Lead-Bismuth eutectic (LBE) cooled SPARK-NC core - Sohail Ahmad Raza; Muhammad Hashim; Liangzhi Cao; Xianan Du; Longwen Jiang (Annals of Nuclear Energy, 2025)

Exploring hotspots of traffic accidents in Chiniot-Sargodha Road, Punjab, Pakistan - Taimoor Ashraf; Muhammad Irfan Ahamad; Shakeel Mahmood; Jiangtao Fu; Muhammad Sajid Mehmood; Adnanul Rehman; Sohail Abbas; Syed Ali Asad Naqvi; Rana Muhammad Zulqarnain (Environment, Development and Sustainability, 2025)

Comparative Nutritional Profiling of Economically Important Shrimp Species in Pakistan - Muhammad Bhatti; Shahid Sherzada; Sohail Ahmad; Muhammad Qazi; Amina Ayub; Saeed Khan; Muhammad Khan; Iqra Rani; Nimra Hussain; Joanna Nowosad; Dariusz Kucharczyk (Journal of Marine Science and Engineering, 2025)
Shrimp are widely recognized as a nutritious and flavorful food choice due to their tender and delicious meat. This study evaluated the nutritional composition of three economically important shrimp species: Penaeus merguiensis, Penaeus monodon, and Penaeus indicus, collected from the coastal areas of Pakistan. All shrimp species were found to be high in protein and low in fat content. The ratio of essential amino acids (EAAs), non-essential amino acids (NEAAs), and total amino acids (TAAs) varied significantly (p ≤ 0.05) among species, with P. indicus showing slightly higher values. Regarding fatty acid analysis, total saturated fatty acid content was found to be 35.04% in P. merguiensis, 52.43% in P. monodon, and 44.77% in P. indicus. Similarly, the polyunsaturated fatty acid content was found to be 26.24%, 26.77%, and 24.74%, in P. merguiensis, P. monodon, and P. indicus, respectively. Based on nutrient yield, P. monodon stands out as the most nutrient-dense species, followed by P. indicus and P. merguiensis. Overall, the present study suggests that all shrimp species can be used as a healthy choice of food and a good source of animal protein for human consumption. These findings provide valuable insights into the role of shrimp in promoting a healthy and balanced diet.

Investigating Bemisia tabaci (Hemiptera: Aleyrodidae) resistance mechanisms: a comprehensive analysis of variable responses to selective insecticides - Dilbar Hussain; Muhammad Saleem; Muhammad Sohail Qadir; Kanwal Hanif; Faisal Hafeez; Usama Saleem; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal; Muhammad Zubair (International Journal of Tropical Insect Science, 2025)

Automatic visual recognition, detection and classification of weeds in cotton fields based on machine vision - Muhammad Sohail Memon; Shuren Chen; Baoguo Shen; Runzhi Liang; Zhong Tang; Shuai Wang; Weiwei Zhou; Noreena Memon (Crop Protection, 2025)

Recent advancements in novel quantum 2D layered materials hybrid photodetectors from IR to THz: From principles to performance enhancement strategies - Muhammad Abdullah; Muhammad Younis; Muhammad Tahir Sohail; Muhammad Asif; Yin Jinde; Yan Peiguang; Qu Junle; Zheng Ping (Chemical Engineering Journal, 2025)

Comparative analysis to assess food security in south asian nations: an application of multivariate GARCH model - Shazia Kousar; Amina Ameer; Adeel Nasir; Muhammad Afzal; Sohail Abbas (Environment, Development and Sustainability, 2024)

Enhancing crop model parameter estimation across computing environments: Utilizing the GLUE method and parallel computing for determining genetic coefficients - Thiago Berton Ferreira; Vakhtang Shelia; Cheryl Porter; Patricia Moreno Cadena; Montserrat Salmeron Cortasa; Muhammad Sohail Khan; Willingthon Pavan; Gerrit Hoogenboom (Computers and Electronics in Agriculture, 2024)

From stress to resilience: Unraveling the molecular mechanisms of cadmium toxicity, detoxification and tolerance in plants - Iqra Noor; Hamza Sohail; Muhammad Tanveer Akhtar; Jiawen Cui; Zhaogeng Lu; Salma Mostafa; Mirza Hasanuzzaman; Sajjad Hussain; Nan Guo; Biao Jin (Science of The Total Environment, 2024)

Nanoarchitectonics of molybdenum rich crown shaped polyoxometalates based ionic liquids reinforced on magnetic nanoparticles for the removal of microplastics and heavy metals from water - Hameed Ullah; Taghrid S. Alomar; Muhammad Tariq; Najla AlMasoud; Moazzam H. Bhatti; Muhammad Ajmal; Zahra Nazar; Muhammad Nadeem; Hafiz Muhammad Asif; Muhammad Sohail (Journal of Environmental Chemical Engineering, 2024)

Trimetallic-doped carbon nitride achieves chondroitin sulfate degradation via a free radical degradation strategy - Xiao-jun Lin; Meng-ting Chang; Min Cao; Muhammad Sohail; Meng Qiao; Xing Zhang (Carbohydrate Polymers, 2024)

Bridging drug discovery through hierarchical subtractive genomics against asd, trpG, and secY of pneumonia causing MDR Staphylococcus aureus - Ayesha Wisal; Nida Saeed; Muhammad Aurongzeb; Muhammad Shafique; Saman Sohail; Waheed Anwar; Zarrin Basharat; Muhammad Irfan; Asad Ullah; Syed S. Hassan (Molecular Genetics and Genomics, 2024)

Application of zinc nanoparticles as seed priming agent improves growth and yield of wheat seedlings grown under salinity stress by enhanced antioxidants activities and gas exchange attributes - Sara Zafar; Shahbaz Khan; Danish Ibrar; Muhammad Kamran Khan; Zuhair Hasnain; Kashf Mehmood; Afroz Rais; Safia Gul; Sohail Irshad; Muhammad Nawaz (Cereal Research Communications, 2024)

Correction: Determination of Toxic Elements in Cannabinoid and Opioid Drugs and Their Impact on Addicts’ Health: A Comparative Study - Ahsanullah Unar; Oan Muhammad Sahito; Laila Alsawalha; Hassan Imran Afridi; Farid Shokry Ataya; Muhammad Sohail Bashir; Dalia Fouad; Farah Naz Talpur; Naveed Ali (Biological Trace Element Research, 2024)

Determination of Toxic Elements in Cannabinoid and Opioid Drugs and Their Impact on Addicts’ Health: A Comparative Study - Ahsanullah Unar; Oan Muhammad Sahito; Laila Alsawalha; Hassan Imran Afridi; Farid Shokry Ataya; Muhammad Sohail Bashir; Dalia Fouad; Farah Naz Talpur; Naveed Ali (Biological Trace Element Research, 2024)

Thermal-hydraulic performance and safety assessment of an LBE-cooled reactor under steady-state and unprotected transients - Muhammad Hashim; Liangzhi Cao; Hongchun Wu; Xiaoqian Jia; Jinshun Wang; Sohail Ahmad Raza; Haoyu Fan (Annals of Nuclear Energy, 2024)

Knockdown of the glucosamine-6-phosphate N-acetyltransferase gene by RNA interference enhances the virulence of entomopathogenic fungi against rice leaffolder Cnaphalocrocis medinalis - Muhammad Shakeel; Ashraf Khan; Juan Du; Abdul Basit; Guangming Yang; Khalid Haddi; Sohail Abbas; Aleena Alam; Shangwei Li (Pesticide Biochemistry and Physiology, 2024)

Comprehensive assessment of heavy metal contamination in soil-plant systems and health risks from wastewater-irrigated vegetables - Muhammad Anis Aslam; Muhammad Sohail Abbas; Muhammad Mustaqeem; Maryam Bashir; Adeeba Shabbir; Muhammad Talha Saeed; Rana Muhammad Irfan (Colloids and Surfaces C: Environmental Aspects, 2024)

Spatial patterned solar evaporator for effective thermal management in enhanced solar-driven evaporation, and wastewater remediation - Naila Arshad; Muhammad Sohail Asghar; Muhammad Sultan Irshad; Najah Alwadie; Jinhua Li; M.A.K Yousaf Shah; Zhengbiao Ouyang; Hao Wang; Ho Xuan Nang; Van-Duong Dao; Xianbao Wang (Chemical Engineering Journal, 2024)

Assessment of residues from common pesticides and associated risks in Pakistan - Muneer Abbas; Sohail Abbas; Niaz Hussain; Muhammad Tariq Javeed; Abdul Ghaffar; Muhammad Nadeem; Mudassar Khaliq; Sana Ullah; Zubeda Parveen; Khalid Ali Khan; Hamed A. Ghramh (Environmental Monitoring and Assessment, 2024)

Biochemical analysis and fertilization success of Cirrhinus mrigala ova during induced spawning - Shahid Sherzada; Tanveer Ahmad; Saeed Akram Khan; Muhammad Inayat; Sohail Ahmad; Abdur Rahman (Animal Reproduction Science, 2024)

An Adaptive Approach in Polymer-Drug Nanoparticle Engineering using Slanted Electrohydrodynamic Needles and Horizontal Spraying Planes - Amna Ali; Saman Zafar; Manoochehr Rasekh; Tahir Ali Chohan; Francesca Pisapia; Neenu Singh; Omar Qutachi; Muhammad Sohail Arshad; Zeeshan Ahmad (AAPS PharmSciTech, 2024)

Toxicity of different nitrogenous fertilizers on Aedes aegypti larvae (Linnaeus) (Diptera: Culicidae) - Sikander Ali; Unsar Naeem-Ullah; Naeem Iqbal; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Shafqat Saeed; Muhammad Usman; Muhammad Nadir Naqqash (International Journal of Tropical Insect Science, 2024)

Global distribution and definitive host range of Echinococcus species and genotypes: A systematic review - Rehman Ali; Shahid Nazeer; Malik Muhammad Sohail Elahi; Emmanuel Gideon Idu; Hongteng Zhang; Hossein Mahmoudvand; Shahid Niaz Khan; Jun Yang (Veterinary Parasitology, 2024)

Exploring the potential of nanomedicine for gene therapy across the physicochemical and cellular barriers - Huma Hameed; Hafiz Shoaib Sarwar; Komel Younas; Muhammad Zaman; Muhammad Jamshaid; Ali Irfan; Maha Khalid; Muhammad Farhan Sohail (Functional & Integrative Genomics, 2024)

Regression-based prediction of flow-induced dominant vibrational frequencies in two-phase flow regimes - Muhammad Sohail; William Pao; Abdul Rahim Othman; Huzaifa Azam; Muhammad Rehan Khan (Ocean Engineering, 2024)

Xylanase from Neobacillus sedimentimangrovi UE25: Characterization, purification and applications - Rozina Rashid; Uroosa Ejaz; Syed Faraz Moin; Muhammad Sohail (Biocatalysis and Agricultural Biotechnology, 2024)

Impact of different range areas on behavior, welfare, and performance of Naked Neck chickens - Saba Zahid; Muhammad Usman; Hafiz Muhammad Ishaq; Muhammad Faizan Haider; Mian Mubashar Saleem; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad; Tarek Amin Ebeid (Tropical Animal Health and Production, 2024)

Computational analysis of fluid dynamics in open channel with the vegetated spur dike - Sohail Iqbal; Muhammad Siddique; Ali Hamza; Nadir Murtaza; Ghufran Ahmed Pasha (Innovative Infrastructure Solutions, 2024)

Retraction Note: pH-responsive CAP-co-poly(methacrylic acid)-based hydrogel as an efficient platform for controlled gastrointestinal delivery: fabrication, characterization, in vitro and in vivo toxicity evaluation - Syed Ahmed Shah; Muhammad Sohail; Muhammad Usman Minhas; Nisar-ur-Rehman; Shahzeb Khan; Zahid Hussain; Mudassir; Arshad Mahmood; Mubeen Kousar; Asif Mahmood (Drug Delivery and Translational Research, 2024)

Geospatial identification of possible rainwater harvesting locations within a high-altitude Gilgit River basin, Pakistan - Madiha Asif; Muhammad Yaseen; Syed Umair Shahid; Yasir Latif; Salma Anwar; Sohail Abbas (Theoretical and Applied Climatology, 2024)
The management of water resources is no longer an option but a necessity especially in countries with a high rate of population growth like Pakistan. Pakistan has a high-water scarcity, an extremely varying topography, and is also one of the countries encountering the problem of climate change. Therefore, prudent utilization of available water resources is a matter in the plains of Pakistan as in its high-altitude regions. Instead of wasting water which is a valuable resource, rainwater harvesting is a way of saving rainwater as an alternative source of fresh water for better use. The aim of this study was to search for potential rainwater-harvesting areas in a high-altitude Gilgit River basin. This research employed the SCS-CN technique in estimating surface runoff in the GIS environment. The geospatial study used four input parameters: slope of the land, land covers, surface runoff and drainage density. The research concluded that some lands, especially those that are deserted in dry area and agricultural lands, can serve as the sites of rainwater harvesting, with only 4% of area that was highly suitable for the purpose. Nevertheless, 37% of the investigated area was shown as totally unviable for rainwater collection installations because of steep slopes and substantial volume of snow. Simultaneously, the rainwater storage design solutions suggested were check dam, percolation tank, and agricultural ponds with the area of 3.5%, 1%, and 0.75% of the given land area, respectively, for rainwater harvesting. The locations of potential catchment and planned rainwater harvesting structures would assist the local authorities and the policy makers to provide plans and design on the construction of water storages and also the optimization of water use.

Phytochemical-mediated regulation of aflatoxigenic fungi contamination in a shifting climate and environment - Shah Zaman; Nasrullah Khan; Muhammad Zahoor; Riaz Ullah; Ahmed Bari; Sohail (Environmental Geochemistry and Health, 2024)

Insights into phytonutrient profile and postharvest quality management of jackfruit: A review - Jashanpreet Kaur; Zora Singh; Hafiz Muhammad Shoaib Shah; Muhammad Sohail Mazhar; Mahmood Ul Hasan; Andrew Woodward (Critical Reviews in Food Science and Nutrition, 2024)

Assessment of carcinogenic and non-carcinogenic risk of exposure to potentially toxic elements in tea infusions: Determination by ICP-OES and multivariate statistical data analysis - Mahmood Ahmed; Muhammad Ahmad; Muhammad Ayyan Khan; Aamir Sohail; Mudassar Sanaullah; Waqar Ahmad; Dure Najaf Iqbal; Khuram Khalid; Tanveer A. Wani; Seema Zargar (Journal of Trace Elements in Medicine and Biology, 2024)

Global nexus between tourism and sustainable futures: the role of economic growth, globalization and renewables - Lixia Gao; Qamar Ali; Muhammad Rizwan Yaseen; Muhammad Sohail Amjad Makhdum; Samuel Asumadu Sarkodie; Madeeha Nisa; Muhammad Tariq Iqbal Khan (Environment, Development and Sustainability, 2024)

Progress, challenges, and prospects of MOF-based adsorbents for phosphate recovery from wastewater - Muhammad Naveed Afridi; Sawaira Adil; Battuya Byambaa; Muhammad Sohail; Aziz-Ur-Rahim Bacha; Jingwen Wang; Chaolin Li (Journal of Water Process Engineering, 2024)

Transcutaneous Delivery of Dexamethasone Sodium Phosphate Via Microneedle-Assisted Iontophoretic Enhancement – A Potential Therapeutic Option for Inflammatory Disorders - Muhammad Sohail Arshad; Saad Hussain; Saman Zafar; Sadia Jafar Rana; Tahir Ali Chohan; Muhammad Hamza; Kazem Nazari; Zeeshan Ahmad (Pharmaceutical Research, 2024)

Evaluation of Bacillus spp. as biocontrol agents against chili leaf spot caused by Xanthomonas vesicatoria - Sadia Aziz; Saleem Akhtar Jamshed; Tariq Mukhtar; Gulshan Irshad; Shahzada Sohail Ijaz; Muhammad Usman Raja (Journal of Plant Diseases and Protection, 2024)

Berberine ameliorates the progression of primary sclerosing cholangitis by activating farnesoid X receptor - Hassan Hameed; Nida Irshad; Muhammad Abrar Yousaf; Sidra Mumtaz; Imran Sohail (Cell Biochemistry and Biophysics, 2024)

Mitigation of drought stress in Zea mays L. through plant growth-promoting rhizobacteria assisted by foliar sorghum water extract - Raza Ullah; Ayesha Siddiqui; Shoaib Ur Rehman; Muhammad Kamran; Hafiz Tassawar Abbas; Muhammad Awais Khalid; Muhammad Rahil Afzal; Esha Jabbar; Muhammad Irfan Sohail (Acta Physiologiae Plantarum, 2024)

Assessment of textile effluent treatment by immobilized Trametes pubescens MB 89 for plant growth promotion - Uroosa Ejaz; Saima Zakir; Zainul Abideen; Bushra Fahim; Waniya Shaikh; Faryal Shakil; Fizza Haroon Mirza; Syed Wasi Haider; Adnan Khan; Muhammad Sohail (Environmental Science and Pollution Research, 2024)

Nanozyme sensor array based on Fe, Se co-doped carbon material for the discrimination of Sulfur-containing compounds - Enxiang Ren; Haochen Qiu; Zhixuan Yu; Min Cao; Muhammad Sohail; Guo-Ping Lu; Xing Zhang; Yamei Lin (Journal of Hazardous Materials, 2024)

Occurrence of natural enemies in maize and the predatory potential of selected arthropods against fall armyworm in Multan, Pakistan - Saleem Riaz; Muhammad Ishtiaq; Fawad Zafar Ahmad Khan; Ghulam Ali; Mirza Abid Mehmood; Muhammad Sohail Qamar Zaman (International Journal of Tropical Insect Science, 2024)

Correction to: Domperidone nanocrystals with boosted oral bioavailability: fabrication, evaluation and molecular insight into the polymer-domperidone nanocrystal interaction - Stalielson Tatenda Ndlovu; Naseem Ullah; Shahzeb Khan; Pritika Ramharack; Mahmoud Soliman; Marcel de Matas; Muhammad Shahid; Muhammad Sohail; Muhammad Imran; Syed Wadood Ali Shah; Zahid Hussain (Drug Delivery and Translational Research, 2024)

Isolation and characterization of Rhizobium from non-leguminous potato plants: New frontiers in Rhizobium research - Tahir Naqqash; Kauser Abdullah Malik; Asma Imran; Sohail Hameed; Muhammad Shahid; Muhammad Kashif Hanif; Afshan Majeed; Muhammad Arshad; Jan Dirk van Elsas (Biology and Fertility of Soils, 2024)

Leading report of molecular prevalence of tick borne Anaplasma marginale and Theileria ovis in yaks (Bos grunniens) from Pakistan - Muqaddas Nawaz; Rehmat Ullah; Zia Ur Rehman; Muhammad Naeem; Afshan Khan; Mohammed Bourhia; Muhammad Mudassir Sohail; Takbir Ali; Adil Khan; Tanveer Hussain; Furhan Iqbal (Archives of Microbiology, 2024)

Retraction Note: The shadow economy in South Asia: dynamic effects on clean energy consumption and environmental pollution - Muhammad Tayyab Sohail; Sana Ullah; Muhammad Tariq Majeed; Ahmed Usman; Zubaria Andlib (Environmental Science and Pollution Research, 2024)

Human biomonitoring of trace metals from different altitudinal settings of Pakistan - Syed Ali Musstjab Akber Shah Eqani; Ambreen Alamdar; Ismat Nawaz; Syed Sayyam Abbas Shah; Tasawar Khanam; Qurat Ul Ain Hayder; Muhammad Sohail; Ioannis A. Katsoyiannis; Heqing Shen (Environmental Science and Pollution Research, 2024)

Dynamics of soil biota and nutrients at varied depths in a Tamarix ramosissima-dominated natural desert ecosystem: Implications for nutrient cycling and desertification management - Waqar Islam; Fanjiang Zeng; Afzal Ahmed Dar; Muhammad Sohail Yousaf (Journal of Environmental Management, 2024)

Retraction Note: Evaluating toxicity of copper(II) oxide nanoparticles (CuO-NPs) through waterborne exposure to tilapia (Oreochromis mossambicus) by tissue accumulation, oxidative stress, histopathology, and genotoxicity - Khurram Shahzad; Muhammad Naeem Khan; Farhat Jabeen; Nasreen Kosour; Abdul Shakoor Chaudhry; Muhammad Sohail (Environmental Science and Pollution Research, 2024)

Recent trends in wastewater treatment by using metal-organic frameworks (MOFs) and their composites: A critical view-point - Syed Shoaib Ahmad Shah; Manzar Sohail; Ghulam Murtza; Amir Waseem; Aziz ur Rehman; Iftikhar Hussain; Muhammad Sohail Bashir; Saleh S. Alarfaji; Ahmed M. Hassan; Muhammad Altaf Nazir; Muhammad Sufyan Javed; Tayyaba Najam (Chemosphere, 2024)

Does environmental policy stringency reduce trade in energy resources? Insights from coal, petroleum, and gas - Ahmed Usman; Sana Ullah; Ilhan Ozturk; Sidra Sohail; Muhammad Tayyab Sohail (Resources Policy, 2024)

How do digital inclusion and energy security risks affect mineral resources trade? Evidence from world-leading mineral trading countries - Muhammad Tayyab Sohail; Norashidah Md Din (Resources Policy, 2024)

Development and Characterization of Glimepiride-Loaded Polymeric Nanoparticles: Formulation Design and Evaluation - Zaiba Irfan; Muhammad Imran Khan; Muhammad Farhan Sohail; Muhammad Furqan Akhtar; Muhammad Naeem Qaisar; Muhammad Kashif Javed; Fareeha Anwar; Badarqa-tul-Ayesha; Majid Anwar; Aslam Khan; Faizan Akram (Journal of Pharmaceutical Innovation, 2024)

Harnessing aptamers for the biosensing of cell surface glycans – A review - Sirui Liu; Furong Zhao; Ke Xu; Min Cao; Muhammad Sohail; Bingzhi Li; Xing Zhang (Analytica Chimica Acta, 2024)

Advances/Scope and prospects of g-C3N4 derived fascinating photocatalyst as a leading route towards solar energy adaption - Asif Hayat; Muhammad Sohail; Zeeshan Ajmal; Hala H. Abd El-Gawad; Djamel Ghernaout; Yas Al-Hadeethi; Saleem Raza; Yasin Orooji (Journal of Cleaner Production, 2024)

Corporate social responsibility—an antidote for sustainable business performance: interconnecting role of digital technologies, employee eco-behavior, and tax avoidance - Syed Abdul Rehman Khan; Adnan Ahmed Sheikh; Muhammad Sohail Tahir (Environmental Science and Pollution Research, 2023)

How does formal credit promote green entrepreneurship? New insights from renewable energy producers in high-, middle-, and low-income countries - Muhammad Tayyab Sohail; Norashidah Md Din (Environmental Science and Pollution Research, 2023)

Impact of different light intensities to Japanese quail eggs on hatching results and post-hatch performance - Shaheryar Ali; Shahid Sherzada; Muhammad Usman; Ehsaan Ullah Khan; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Effects of prenatal dichromatic light exposure on hatching results and post-hatch performance of Japanese quail - Muhammad Safwan; Shahid Mehmood; Shahid Sherzada; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Shaheryar Ali; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; et al. (Tropical Animal Health and Production, 2023)

Subtractive sequence analysis aided druggable targets mining in Burkholderia cepacia complex and finding inhibitors through bioinformatics approach - Syed Shah Hassan; Rida Shams; Ihosvany Camps; Zarrin Basharat; Saman Sohail; Yasmin Khan; Asad Ullah; Muhammad Irfan; Javed Ali; Muhammad Bilal; Carlos M. Morel (Molecular Diversity, 2023)

Elucidating the Mechanistic Role of Zinc-Lysine to Enhance Cd Tolerance in Diverse Wheat (Triticum aestivum L.) Cultivars Through Distinct Morpho-Physio-Biochemical Improvements Under Cd Stress - Muhammad Hussaan; Saghir Abbas; Qasim Ali; Muhammad Sohail Akram; Kashif Tanwir; Ahmad Raza; Sherjeel Hashmat; Muhammad Aqeel; Hassan Javed Chaudhary; Muhammad Tariq Javed (Journal of Soil Science and Plant Nutrition, 2023)

Fabrication and Evaluation of Differential Release Bilayer Tablets of Clarithromycin and Levofloxacin by 3D Printing - Qazi Amir Ijaz; Sumera Latif; Sumaira Irum Khan; Memoona Rashid; Hafsa Afzal; Nasrullah Jan; Zeeshan Javaid; Muhammad Sarfraz; Amjad Hussain; Muhammad Sohail Arshad; Nadeem Irfan Bukhari; Nasir Abbas (Journal of Pharmaceutical Innovation, 2023)

Preparation of Tamsulosin Hydrochloride-Loaded Mucoadhesive In Situ Gelling Polymeric Formulation for Nasal Delivery in Geriatrics - Sadia Jafar Rana; Saman Zafar; Aqeel Shahzad; Muhammad Basit; Jahanzeb Mudassir; Muhammad Akhlaq; Tahir Ali Chohan; Muhammad Sohail Arshad (AAPS PharmSciTech, 2023)

Green development in BRICS: unraveling the effects of environmental technology, R&D spending, and green investment in the context of COP21 - Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2023)

Size-resolved ambient bioaerosols concentration, antibiotic resistance, and community composition during autumn and winter seasons in Qatar - Bilal Sajjad; Kashif Rasool; Azhar Siddique; Khadeeja Abdul Jabbar; Shimaa S. El-Malaha; Muhammad Umar Sohail; Fares Almomani; M. Rami Alfarra (Environmental Pollution, 2023)

Exploring perovskite oxide for advancing salt-resistant photothermal membranes and reliable thermoelectric generators - Naila Arshad; Muhammad Sultan Irshad; Muneerah Alomar; Jinming Guo; M. Sohail Asghar; Naveed Mushtaq; M.A.K. Yousaf; Uzma Ghazanfar; Matiullah Shah; Xianbao Wang; Yabin Hao; Lien Thi Do; et al. (Chemical Engineering Journal, 2023)

Drug–ionic surfactant interactions: density, sound speed, spectroscopic, and electrochemical studies - Muhammad Sohail; Hafiz Muhammad Abd Ur Rahman; Muhammad Nadeem Asghar (European Biophysics Journal, 2023)

Rural areas development and pro-environmental behavior in China: implications for rural development and planning - Xiaoli Cao; Yingxia Yun; Lijian Ren; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2023)

The impact of CSR and green consumption on consumer satisfaction and loyalty: moderating role of ethical beliefs - Sohail Ahmad; Muhammad Irfan Shakir; Afshan Azam; Shahid Mahmood; Qingyu Zhang; Zaheer Ahmad (Environmental Science and Pollution Research, 2023)

Emerging trends in insect sex pheromones and traps for sustainable management of key agricultural pests in Asia: beyond insecticides—a comprehensive review - Aleena Alam; Sohail Abbas; Arzlan Abbas; Muneer Abbas; Faisal Hafeez; Muhammad Shakeel; Feng Xiao; Chen Ri Zhao (International Journal of Tropical Insect Science, 2023)

Estimating hardness and Young's modulus of shale using drill cuttings: Implications for hydraulic fracturing in shale gas reservoir development - Ghulam Mohyuddin Sohail; Qamar Yasin; Ahmed E. Radwan; Muhammad Zaka Emad (Gas Science and Engineering, 2023)

RETRACTED: A facile two-step hydrothermal preparation of 2D/2D heterostructure of Bi2WO6/WS2 for the efficient photodegradation of methylene blue under sunlight - Muhammad Fiaz; Manzar Sohail; Ayman Nafady; Geoffrey Will; Md A. Wahab (Environmental Research, 2023)

Synthesis of MXene-based single-atom catalysts for energy conversion applications - Muhammad Aizaz Ud Din; Syed Shoaib Ahmad Shah; Muhammad Sufyan Javed; Manzar Sohail; Aziz ur Rehman; Muhammad Altaf Nazir; Mohammed A. Assiri; Tayyaba Najam; Nanpu Cheng (Chemical Engineering Journal, 2023)

Comparative evaluation of different moulting methods on productive performance, egg quality, and antibody response of leghorn hens - Amir Saeed; Shahid Mehmood; Muhammad Shahid Zahoor; Ehsaan Ullah Khan; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Sustainable development through corporate social responsibility adoption and its drivers: evidence from corporate industrial sector - Hussain Bux; Zhe Zhang; Muhammad Tayyab Sohail; Naveed Ahmad; Adnan Ali (Environmental Science and Pollution Research, 2023)

Micro- and nanoplastics: Contamination routes of food products and critical interpretation of detection strategies - Muhammad Sohail; Zunaira Urooj; Sobia Noreen; Mirza Muhammad Faran Ashraf Baig; Xing Zhang; Bingzhi Li (Science of The Total Environment, 2023)

Polyoxyethylene Lauryl Ether (Brij-35) and Poloxamer 407–Based Non-ionic Surfactant Vesicles for Dissolution Enhancement of Tacrolimus - Razia Hanif; Muhammad Imran Khan; Asadullah Madni; Muhammad Furqan Akhtar; Muhammad Farhan Sohail; Ammara Saleem; Mubashar Rehman; Sufyan Junaid Usmani; Aslam Khan; Athar Masood (Journal of Pharmaceutical Innovation, 2023)

Cloning and functional analysis of the DXR gene and promoter region in Osmanthus fragrans var. semperflorens - Zihan Wang; Taimoor Hassan Farooq; Hanjie He; Aitzaz A.A. Shahani; Rashida Hameed; Amna Fayyaz; Muhammad Sohail Yousaf; Jun Wang; Lili Chen (Functional & Integrative Genomics, 2023)

Exploring and targeting potential druggable antimicrobial resistance targets ArgS, SecY, and MurA in Staphylococcus sciuri with TCM inhibitors through a subtractive genomics strategy - Aafareen Khan; Saman Sohail; Seerat Yaseen; Sareen Fatima; Ayesha Wisal; Sufyan Ahmed; Mahrukh Nasir; Muhammad Irfan; Asad Karim; Zarrin Basharat; Yasmin Khan; Muhammad Aurongzeb; et al. (Functional & Integrative Genomics, 2023)

Evaluating policy-driven capital for renewable energy investments in the presence of cross-sectional dependence: perspectives from financial institutions and markets - Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2023)

Global digital divide and environmental degradation in Africa - Sana Sarwar; Muhammad Rizwan Yaseen; Muhammad Sohail Amjad Makhdum; Azeem Sardar; Nazia Yasmeen; Rameen Shahid (Environmental Science and Pollution Research, 2023)

Evaluating the effects of soil physicochemical properties under different land use types in the arid zones of Pakistan - Muhammad Yaseen; Sohail Abbas; Yasir Latif (Environment, Development and Sustainability, 2023)

Feed intake, feeding behavior, growth performance, nutrient digestibility, and carcass characteristics of goats fed pelleted total mixed rations with varying Rhodes hay levels - Muhammad Irfan Malik; Xuezhao Sun; Muhammad Afzal Rashid; Muhammad Amer Sohail; Muhammad Shahbaz Yousaf; Habib Ur Rehman; Imran Mohsin; Jianping Li (Small Ruminant Research, 2023)

Colloidal gold based immunochromatographic detection of Mycoplasmopsis synoviae infection and its prevalence in avian species of Karachi, Pakistan - Nida Rehman; Uroosa Ejaz; Amal Siraj; Shazma Liaquat; Muhammad Sohail; Taseer Ahmed Khan; Syed Faraz Moin; Aqeel Ahmad (Research in Veterinary Science, 2023)

Enhanced Degradation of Acid Orange 52 Using a Polyextremophilic Ascomycete in Stirred Tank Bioreactor - Qandeel Laraib; Maryam Shafique; Muhammad Ali Versiani; Khitab Gul; Uroosa Ejaz; Haji Muhammad; Sehar Afshan Naz; Drauzio E. N. Rangel; Alene Alder-Rangel; Kousar Yasmeen; Nusrat Jabeen; Jing Liu; et al. (Water, Air, & Soil Pollution, 2023)

Single Pot Enzymatic Treatment of Sugarcane Bagasse Using Laccase and Cellulase for the Production of Value-Added Products - Usama Hafeez; Muhammad Sohail; Syed Tariq Ali (Sugar Tech, 2023)

Improved Transdermal Delivery of Rabies Vaccine using Iontophoresis Coupled Microneedle Approach - Muhammad Sohail Arshad; Saad Hussain; Saman Zafar; Sadia Jafar Rana; Nadia Ahmad; Najmusama Abdul Jalil; Zeeshan Ahmad (Pharmaceutical Research, 2023)

Exploring the nexus between green innovations and green growth in G-7 economies: evidence from wavelet quantile correlation and continuous wavelet transform causality methods - Umer Zaman; Muhammad Zubair Chishti; Touseef Hameed; Muhammad Sohail Akhtar (Environmental Science and Pollution Research, 2023)

Plant disease management with amelioration of systemic resistance in soybean by endophytic fungi associated with GC-MS metabolic profiling of Chaetomium sp., - Hafiza Farhat; Faizah Urooj; Nida Sohail; Shahid Ullah; Muhammad Shaiq Ali (Physiological and Molecular Plant Pathology, 2023)

Soil organic carbon sequestration and modeling under conservation tillage and cropping systems in a rainfed agriculture - Sana ur Rehman; Shahzada Sohail Ijaz; Muhammad Ali Raza; Atta Mohi Ud Din; Khalid Saifullah Khan; Shroz Fatima; Taqi Raza; Sajid Mehmood; Amjad Saeed; Muhammad Ansar (European Journal of Agronomy, 2023)

Balancing nitrate acquisition strategies in symbiotic legumes - Zainab Rahmat; Muhammad N. Sohail; Francine Perrine-Walker; Brent N. Kaiser (Planta, 2023)
Main conclusion Legumes manage both symbiotic (indirect) and non-symbiotic (direct) nitrogen acquisition pathways. Understanding and optimising the direct pathway for nitrate uptake will support greater legume growth and seed yields. Abstract Legumes have multiple pathways to acquire reduced nitrogen to grow and set seed. Apart from the symbiotic N 2 -fixation pathway involving soil-borne rhizobia bacteria, the acquisition of nitrate and ammonia from the soil can also be an important secondary nitrogen source to meet plant N demand. The balance in N delivery between symbiotic N (indirect) and inorganic N uptake (direct) remains less clear over the growing cycle and with the type of legume under cultivation. In fertile, pH balanced agricultural soils, NO 3 − is often the predominant form of reduced N available to crop plants and will be a major contributor to whole plant N supply if provided at sufficient levels. The transport processes for NO 3 − uptake into legume root cells and its transport between root and shoot tissues involves both high and low-affinity transport systems called HATS and LATS, respectively. These proteins are regulated by external NO 3 − availability and by the N status of the cell. Other proteins also play a role in NO 3 − transport, including the voltage dependent chloride/nitrate channel family (CLC) and the S-type anion channels of the SLAC/SLAH family. CLC’s are linked to NO 3 − transport across the tonoplast of vacuoles and the SLAC/SLAH’s with NO 3 − efflux across the plasma membrane and out of the cell. An important step in managing the N requirements of a plant are the mechanisms involved in root N uptake and the subsequent cellular distribution within the plant. In this review, we will present the current knowledge of these proteins and what is understood on how they function in key model legumes ( Lotus japonicus, Medicago truncatula and Glycine sp.). The review will examine their regulation and role in N signalling, discuss how post-translational modification affects NO 3 − transport in roots and aerial tissues and its translocation to vegetative tissues and storage/remobilization in reproductive tissues. Lastly, we will present how NO 3 − influences the autoregulation of nodulation and nitrogen fixation and its role in mitigating salt and other abiotic stresses.

Radiological risk assessment from the Gamma spectrometry of soil samples in the vicinity of a research centre in Nilore, Pakistan - Tahira Shabbir; Muhammad Sohail; Rizwan Ahmed; Masroor Ahmad; Khizar Hayat Satti (Environmental Monitoring and Assessment, 2023)

Unveiling the genomic potential of a novel thermostable glycoside hydrolases producing Neobacillus sedimentimangrovi UE25 - Uroosa Ejaz; Faizan Saleem; Rozina Rashid; Khwaja Ali Hasan; Muhammad Noman Syed; Muhammad Sohail (Antonie van Leeuwenhoek, 2023)

Temporal study of wastewater surveillance from September 2020 to March 2021: an estimation of COVID-19 patients in Lahore, Pakistan - Muhammad Adnan Ashraf; Muhammad Nawaz; Ali Asif; Muhammad Asad Ali; Adnan Mehmood; Muhammad Waqar Aziz; Muhammad Zubair Shabbir; Nadia Mukhtar; Muhammad Abu Bakr Shabbir; Sohail Raza; Tahir Yaqub (Environmental Science and Pollution Research, 2023)

Correction to: The impact of geopolitical risk, governance, technological innovations, energy use, and foreign direct investment on CO2 emissions in the BRICS region - Ijaz Uddin; Muhammad Usman; Najia Saqib; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2023)

RETRACTED: Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2023)

Optimizing the dynamics of bone turnover with genetic algorithm - Muhammad Idrees; Ayesha Sohail (Modeling Earth Systems and Environment, 2023)

Numerical investigation of thermal-hydraulic design of a printed circuit steam generator - Muhammad Ali Khan; Syed Anas Sohail; Khalid Waheed; Waseem Siddique; Muhammad Ilyas; Fatih Aydogan; Kamran Rasheed Qureshi; Imran Shaban Bhatti (Annals of Nuclear Energy, 2023)

The impact of geopolitical risk, governance, technological innovations, energy use, and foreign direct investment on CO2 emissions in the BRICS region - Ijaz Uddin; Muhammad Usman; Najia Saqib; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2023)

Enhancing carbon capture efficiency of zeolite-embedded polyether sulfone mixed-matrix membranes via annealing process - Aamir Sohail; Muhammad Sarfraz; Sidra Nawaz; Zaman Tahir (Journal of Cleaner Production, 2023)

Performance assessment of gridded climatic data and modeling spatial accuracy ranking matrix for gridded precipitation using a new pixel-based approach: a district-wise case study of Punjab - Muhammad Usman Saleem; Mian Sohail Akram (Arabian Journal of Geosciences, 2023)

Country risk and its impact on renewable energy investment in highly polluted economies - Huang Ren; Xu Qifeng; Guan Yongjun; Xu Yunbao; Hu Gaole; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2023)

LC-ESI-QTOF-MS/MS profiling of phenolic compounds in Australian native plums and their potential antioxidant activities - Jiaxun Li; Haoyao Liu; Muhammad Sohail Mazhar; Salman Quddus; Hafiz Ansar Rasul Suleria (Food Bioscience, 2023)

Recent Innovations in Non-dairy Prebiotics and Probiotics: Physiological Potential, Applications, and Characterization - Fasiha Fayyaz Khan; Asma Sohail; Shakira Ghazanfar; Asif Ahmad; Aayesha Riaz; Kashif Sarfraz Abbasi; Muhammad Sohail Ibrahim; Mohammad Uzair; Muhammad Arshad (Probiotics and Antimicrobial Proteins, 2023)

Isolation, characterization and larvicidal potential of indigenous soil inhabiting bacteria against larvae of southern house mosquito (Culex quinquefasciatus Say) - Sohaib Iftikhar; Muhammad Asam Riaz; Muhammad Zeeshan Majeed; Muhammad Afzal; Anam Ali; Mubshara Saadia; Zulfiqar Ali; Sohail Ahmed (International Journal of Tropical Insect Science, 2023)

Staphylococcus Sciuri SAT-17 Facilitated in Vitro Regenerated Sugarcane Plantlets Cultivation in Saline Soil by Harmonizing Oxidative Signaling, Photosynthetic Efficiency and Nutrients Uptake Patterns - Raheel Parvez Abbasi; Muhammad Sohail Akram; Khadija Rafiq; Saadia Basheer; Naeem Iqbal (Journal of Soil Science and Plant Nutrition, 2023)

Engineering of tetanus toxoid-loaded polymeric microneedle patches - Muhammad Sohail Arshad; Shafaq Gulfam; Saman Zafar; Najmusama Abdul Jalil; Nadia Ahmad; Omar Qutachi; Ming-Wei Chang; Neenu Singh; Zeeshan Ahmad (Drug Delivery and Translational Research, 2023)

Nanoparticles assisted regulation of oxidative stress and antioxidant enzyme system in plants under salt stress: A review - Muhammad Zia-ur-Rehman; Sidra Anayatullah; Effa Irfan; Syed Makhdoom Hussain; Muhammad Rizwan; Muhammad Irfan Sohail; Muhammad Jafir; Tanveer Ahmad; Muhammad Usman; Hesham F. Alharby (Chemosphere, 2023)

Photocatalytic degradation of industrial dye using hybrid filler impregnated poly-sulfone membrane and optimizing the catalytic performance using Box-Behnken design - Sadaf Ul Hassan; Sidra Shafique; Bushra Anees Palvasha; Muhammad Haris Saeed; Syed Ali Raza Naqvi; Sohail Nadeem; Syed Irfan; Toheed Akhter; Asim Laeeq Khan; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Determinants of CSR and green purchase intention: Mediating role of customer green psychology during COVID-19 pandemic - Wasim Ahmad; Rana Muhammad Sohail Jafar; Abdul Waheed; Huaping Sun; Sayed Sibtain Ali Shah Kazmi (Journal of Cleaner Production, 2023)

Effects of age, body weight, semen collection frequency and holding duration on semen traits of broiler breeder reared under different housing systems - Muhammad Shabir Shaheen; Sadaf Aslam; Shahid Mehmood; Muhammad Tariq; Yassar Abbas; Hassan Ashfaq; Sohail Ahmad (Tropical Animal Health and Production, 2023)

The compressive and tensile behavior of polypropylene fibers and activated fly ash incorporated concrete at elevated temperatures - Muhammad Sohail Jameel; Ali Raza; Mohamed Hechmi El Ouni; Yasser Alashker (European Journal of Environmental and Civil Engineering, 2023)

Improving drought mitigation strategies and disaster risk reduction through MODIS and TRMM-based data in relation to climate change over Pakistan - Shahzad Ali; Abdul Basit; Tyan Alice Makanda; Inamullah; Fahim Ullah Khan; Muhammad Sajid; Tamseela Riaz; Hira Farooq Abbasi; Manzoor; Amir Sohail (Environmental Science and Pollution Research, 2023)

Opportunities and constraints for cleaner production policy in the developing world: a case study of Sindh Region, Pakistan - Love Kumar; Sohail Ali Naqvi; Matthew J. Deitch; Muhammad Jibran Khalid; Komal Naeem; Arjmand Qayyum Amjad; Avinash Kumar; Tesfay Gebretsadkan Gebremicael; Masood Arshad (Environment, Development and Sustainability, 2023)

Two-way strategy for enhanced pectinase production: Random mutagenesis and utilization of a halophytic biomass - Asma Hanif; Uroosa Ejaz; Khwaja Ali Hasan; Malaika Karim; Fehmida Suleman; Muskan Siddiq; Syed Faraz Moin; Zainul Abideen; Muhammad Sohail (Biocatalysis and Agricultural Biotechnology, 2023)

Exploring antibiotic resistance genes, mobile gene elements, and virulence gene factors in an urban freshwater samples using metagenomic analysis - Sohail M. Noman; Muhammad Shafiq; Shabana Bibi; Bharti Mittal; Yumeng Yuan; Mi Zeng; Xin Li; Oluwaseyi Abraham Olawale; Xiaoyang Jiao; Muhammad Irshad (Environmental Science and Pollution Research, 2023)

Do financial development, economic growth, energy consumption, and trade openness contribute to increase carbon emission in Pakistan? An insight based on ARDL bound testing approach - Muhammad Usman; Rakhshanda Kousar; Muhammad Sohail Amjad Makhdum; Muhammad Rizwan Yaseen; Abdul Majeed Nadeem (Environment, Development and Sustainability, 2023)

Examining the potential role of ICT diffusion on green growth: does financial development matter in BRICS economies? - Yuping Tang; Wanling Chen; Shaoming Chen; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2022)

New trends in immunocastration and its potential to improve animal welfare: a mini review - Sohail Ahmed; Xunping Jiang; Guiqiong Liu; Amber Sadiq; Umar Farooq; Teketay Wassie; Ali Haider Saleem; Muhammad Zubair (Tropical Animal Health and Production, 2022)

Identification and primary distribution of Citrus viroid V in citrus in Punjab, Pakistan - Amjad Ali; Ummad ud din Umar; Sohail Akhtar; Muhammad Taimoor Shakeel; Ateeq ur Rehman; Muhammad Nouman Tahir; Sagheer Atta; Mahmoud Moustafa; Fatih Ölmez; Rashida Parveen (Molecular Biology Reports, 2022)

Pterostilbene improves CFA-induced arthritis and peripheral neuropathy through modulation of oxidative stress, inflammatory cytokines and neurotransmitters in Wistar rats - Ayesha Amin; Muhammad Furqan Akhtar; Ammara Saleem; Ali Sharif; Shahid Shah; Muhammad Imran Khan; Fareeha Anwar; Ghulam Abbas; Hafiz Muhammad Zubair; Muhammad Farhan Sohail (Inflammopharmacology, 2022)

Revealing the effectiveness of environmental policy stringency and environmental law on environmental performance: does asymmetry matter? - Mingxiang Chen; Sidra Sohail; Muhammad Tariq Majeed (Environmental Science and Pollution Research, 2022)

Bentonite binding with mercury(II) ion through promotion of reactive oxygen species derived from manure-based dissolved organic matter - Saeed Rehman; Sayyaf Yousaf; Quanyun Ye; Liu Chenhui; Muhammad Bilal; Ahson Jabbar Shaikh; Muhammad Saqib Khan; Sohail Anjum Shahzad; Pingxiao Wu (Environmental Science and Pollution Research, 2022)

Spatio-temporal landslide inventory and susceptibility assessment using Sentinel-2 in the Himalayan mountainous region of Pakistan - Alam Sher Bacha; Muhammad Shafique; Harald van der Werff; Mark van der Meijde; Mian Luqman Hussain; Sohail Wahid (Environmental Monitoring and Assessment, 2022)

A PLS-SEM approach to determine farmers’ awareness about climate change mitigation and adaptation strategies: pathway toward sustainable environment and agricultural productivity - Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2022)

Diversity among synthetic backcross-derived wheat (Triticum aestivum L.) lines for drought tolerance - Muhammad Sohail; Maqsood Qamar; Imtiaz Hussain (Euphytica, 2022)

Does education matter in China? Myths about financial inclusion and energy consumption - Yukun Li; Jian Chen; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2022)

Deciphering distinct root exudation, ionomics, and physio-biochemical attributes of Serratia marcescens CP-13 inoculated differentially Cd tolerant Zea mays cultivars - Kashif Tanwir; Muhammad Shahid; Saghir Abbas; Qasim Ali; Muhammad Sohail Akram; Hassan Javed Chaudhary; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2022)

Response of sorghum and millet to poultry and farmyard manure–based biochar treatments - Muhammad Fraz Ali; Ummar Ali; Shahid Bilal; Usman Zulfiqar; Sidra Sohail; Tajamul Hussain (Arabian Journal of Geosciences, 2022)

Determinants of China’s renewable energy industry development: do eco-innovation and financial inclusion matter? - Peng Liu; Xinwei Gao; Lei Yu; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2022)

Review on integrated disease and pest management of field crops - Muneer Abbas; Muhammad Saleem; Dilbar Hussain; Muhammad Ramzan; Muhammad Jawad Saleem; Sohail Abbas; Niaz Hussain; Muhammad Irshad; Khalid Hussain; Ghulam Ghouse; Mudassar Khaliq; Zubeda Parveen (International Journal of Tropical Insect Science, 2022)

Structural and Electronic (Absorption and Fluorescence) Properties of a Stable Triplet Diphenylcarbene: A DFT Study - Abrar Ul Hassan; Ayesha Mohyuddin; Sohail Nadeem; Cihat Güleryüz; Sadaf Ul Hassan; Mohsin Javed; Muhammad Salman Muhsan (Journal of Fluorescence, 2022)

Freely dissolved organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) along the Indus River Pakistan: spatial pattern and risk assessment - Muhammad Sohail; Syed Ali Musstjab Akber Shah Eqani; Habib Bokhari; Muhammad Zaffar Hashmi; Nadeem Ali; Ambreen Alamdar; Joel E. Podgorski; Dave Adelman; Rainer Lohmann (Environmental Science and Pollution Research, 2022)

Asymmetric determinants of CO2 emissions in China: do government size and economic size matter? - Hai Lan; Chengping Cheng; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2022)

Interactive effect of amino acids balanced at ideal lysine ratio and exogenous protease supplemented to low CP diet on growth performance, carcass traits, gut morphology, and serum metabolites in broiler chicken - Muhammad Adeel Maqsood; Ehsaan Ullah Khan; Shafqat Nawaz Qaisrani; Muhammad Afzal Rashid; Muhammad Shabir Shaheen; Azhar Nazir; Hammad Talib; Sohail Ahmad (Tropical Animal Health and Production, 2022)

Asymmetric macroeconomic determinants of energy intensity in China: does economic development matter? - Hai Lan; Chengping Cheng; Muhammad Afaq Haider Jafri; Sidra Sohail (Environmental Science and Pollution Research, 2022)

Decomposing the asymmetric effects of terrorism and FDI on carbon emission: evidence from fragile economies - Xue Gao; Xin Li; Muhammad Zubair Chishti; Sana Ullah; Sidra Sohail (Environmental Science and Pollution Research, 2022)

Multi-step short-term $$PM_{2.5}$$ forecasting for enactment of proactive environmental regulation strategies - Saba Gul; Gul Muhammad Khan; Sohail Yousaf (Environmental Monitoring and Assessment, 2022)

Effects of mirror and coloured balls as environmental enrichment tools on performance, welfare and meat quality traits of commercial broiler - Muhammad Shahid Zahoor; Sohail Ahmad; Muhammad Usman; Muhammad Dawood; Karim El-Sabrout; Syed Ghulam Mohayud Din Hashmi; Ehsaan Ullah Khan; Murrawat Hussain; Muhammad Adeel Maqsood; Hafiz Rao Abdul Latif (Tropical Animal Health and Production, 2022)

In vitro synergy of entomopathogenic fungi and differential-chemistry insecticides against armyworm Spodoptera litura Fabricius (Lepidoptera: Noctuidae) - Zainab Batool; Muhammad Asam Riaz; Samy Sayed; Muhammad Zeeshan Majeed; Sohail Ahmed; Sami Ullah (International Journal of Tropical Insect Science, 2022)

Effects of diverse irrigation with wastewater in soil and plants: assessing the risk of metal to the animal food chain - Zafar Iqbal Khan; Fatima Ghulam Muhammad; Kafeel Ahmad; Shahzad Akhtar; Muhammad Sohail; Muhammad Nadeem; Shahzadi Mahpara; Muhammad Umer Farooq Awan; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Iftikhar Hussain (Environmental Science and Pollution Research, 2022)

Environmental costs of political instability in Pakistan: policy options for clean energy consumption and environment - Muhammad Tayyab Sohail; Muhammad Tariq Majeed; Parvez Ahmed Shaikh; Zubaria Andlib (Environmental Science and Pollution Research, 2022)

Preparation and Quality Attributes of Egg-reduced Pound Cake Incorporating Grass Carp ( Ctenopharyngodonidella ) Protein Concentrate - Sohail Khan; Haroon Shah; Sajid Kamal; Abdur Rehman; Qayyum Shehzad; Umer Karamat; Aiman Karim; Mudassar Hussain; Muhammad Muneeb; Wenshui Xia (Journal of Aquatic Food Product Technology, 2022)

Does financial inclusion and education limit CO2 emissions in China? A new perspective - Nan Liu; Cencen Hong; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2022)

Illuminating Empirical Evidence of Climate Change: Impacts on Rice Production in the Punjab Regions, Pakistan - Sohail Abbas; Shazia Kousar; Safdar Ali Shirazi; Muhammad Yaseen; Yasir Latif (Agricultural Research, 2022)

Assessment of major food crops production-based environmental efficiency in China, India, and Pakistan - Muhammad Shoaib Aslam; Pan Huanxue; Sidra Sohail; Muhammad Tariq Majeed; Saeed ur Rahman; Shoaib Ahmad Anees (Environmental Science and Pollution Research, 2022)

Soil conditioners improve rhizodegradation of aged petroleum hydrocarbons and enhance the growth of Lolium multiflorum - Fida Hussain; Aqib Hassan Ali Khan; Imran Hussain; Asifa Farooqi; Yousaf Shad Muhammad; Mazhar Iqbal; Muhammad Arslan; Sohail Yousaf (Environmental Science and Pollution Research, 2022)

Isolation and molecular characterization of Adenovirus in suspected acute flaccid paralysis patients: A preliminary report from Pakistan - Zainab Khattak; Aamer Ali Shah; Syed Sohail Zahoor Zaidi; Nayab Mahmood; Muhammad Masroor Alam; Salmaan Sharif; Ribqa Akhtar; Yasir Arshid; Muhammad Suleman Rana (Archives of Virology, 2022)

Do economic policy uncertainty and financial development influence the renewable energy consumption levels in China? - Wang Lei; Lihan Liu; Muhammad Hafeez; Sidra Sohail (Environmental Science and Pollution Research, 2022)

Environmental benefit of clean energy consumption: can BRICS economies achieve environmental sustainability through human capital? - Yanyan Liu; Muhammad Tayyab Sohail; Arman Khan; Muhammad Tariq Majeed (Environmental Science and Pollution Research, 2022)

Reducing cooling load and lifecycle cost for residential buildings: a case of Lahore, Pakistan - Huma Khalid; Muhammad Jamaluddin Thaheem; Muhammad Sohail Anwar Malik; Muhammad Ali Musarat; Wesam Salah Alaloul (The International Journal of Life Cycle Assessment, 2021)

Examining the role of non-economic factors in energy consumption and CO2 emissions in China: policy options for the green economy - Lin Jian; Muhammad Tayyab Sohail; Sana Ullah; Muhammad Tariq Majeed (Environmental Science and Pollution Research, 2021)

Asymmetric effects of premature deagriculturalization on economic growth and CO2 emissions: fresh evidence from Pakistan - Sana Ullah; Waheed Ahmad; Muhammad Tariq Majeed; Sidra Sohail (Environmental Science and Pollution Research, 2021)

Assessing the potential for rooftop rainwater harvesting and its physio and socioeconomic impacts, Rawal watershed, Islamabad, Pakistan - Sohail Abbas; Muhammad Junaid Mahmood; Muhammad Yaseen (Environment, Development and Sustainability, 2021)

Tick-borne Diseases in Sheep and Goats in Pakistan: A Systematic Review and Meta-analysis - Aqsa Mushtaq; Tehniat Shoukat; Tanzila Mumtaz; Muhammad Qasim; Kiran Ajmal; Nayab Fatima; Aisha Khan; Misbah Kouser; Nazeer Hussain; Sadia Selim Khan; Mohammed Sohail Afzal; Sami Simsek; et al. (Acta Parasitologica, 2021)

Modeling financial development, tourism, energy consumption, and environmental quality: Is there any discrepancy between developing and developed countries? - Muhammad Usman; Muhammad Rizwan Yaseen; Rakhshanda Kousar; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2021)

Preparation and Characterization of pH-Independent Sustained-Release Tablets Containing Hot Melt Extruded Solid Dispersions of Clarithromycin - Qazi Amir Ijaz; Sumera Latif; Qurat-ul-ain Shoaib; Memoona Rashid; Muhammad Sohail Arshad; Amjad Hussain; Nadeem Irfan Bukhari; Sohail Riaz; Nasir Abbas (AAPS PharmSciTech, 2021)

Facies Analysis and Sedimentary Architecture of Hybrid Event Beds in Submarine Lobes: Insights from the Crocker Fan, NW Borneo, Malaysia - Muhammad Jamil; Numair Ahmed Siddiqui; Nisar Ahmed; Muhammad Usman; Muhammad Umar; Hamad ur Rahim; Qazi Sohail Imran (Journal of Marine Science and Engineering, 2021)
Hybrid event beds represent the combined effect of multiple geological processes, which result in complex depositional geometries and distinct facies distribution in marine environments. Previous work on hybrid event beds highlights the classification, origin, and types of hybrid facies. However, in the present study, we discuss the development of hybrid event beds in submarine lobes with an emphasis on the analysis of proximal to distal, frontal to lateral relationships and evolution during lobe progradation. Detailed geological fieldwork was carried out in the classical deep-marine Late Paleogene Crocker Fan to understand the relationship between the character of hybrid bed facies and lobe architecture. The results indicate that hybrid facies of massive or structureless sandstone with mud clasts, clean to muddy sand, and chaotic muddy sand with oversized sand patch alternations (H1–H3) are well developed in proximal to medial lobes, while distal lobes mainly contain parallel to cross-laminated clean to muddy hybrid facies (H3–H5). Furthermore, lateral lobes have less vertical thickness of hybrid beds than frontal lobes. The development of hybrid beds takes place in the lower part of the thickening upward sequence of lobe progradation, while lobe retrogradation contains hybrid facies intervals in the upper part of stratigraphy. Hence, the development of hybrid beds in submarine lobe systems has a significant impact on the characterization of heterogeneities in deep-marine petroleum reservoirs at sub-seismic levels.

Management of green economy in China and India: dynamics of poverty and policy drivers - Anyin Jiang; Ying Cao; Muhammad Tayyab Sohail; Muhammad Tariq Majeed; Sidra Sohail (Environmental Science and Pollution Research, 2021)

Evaluation of pasture allowance of manganese for ruminants - Xiaoping Ge; Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Mudasra Munir; Muhammad Nadeem; Muhammad Umer Farooq Awan; et al. (Environmental Science and Pollution Research, 2021)

Analysis of income inequality and environmental pollution in BRICS using fresh asymmetric approach - Weijun Zhao; Muhammad Hafeez; Adnan Maqbool; Sana Ullah; Sidra Sohail (Environmental Science and Pollution Research, 2021)

Evaluating the suitability of two parametric wind speed distributions: a case study from Pakistan - Muhammad Ahsan ul Haq; Sohail Chand; Muhammad Zahir Sajjad; Rana Muhammad Usman (Modeling Earth Systems and Environment, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

Geopolitical risks, energy consumption, and CO2 emissions in BRICS: an asymmetric analysis - Weijun Zhao; Ruoyu Zhong; Sidra Sohail; Muhammad Tariq Majeed; Sana Ullah (Environmental Science and Pollution Research, 2021)

Assessment of groundwater intrinsic vulnerability using GIS-based DRASTIC method in District Haripur, Khyber Pakhtunkhwa, Pakistan - Sohail Ahmed; Anwar Qadir; Mumtaz Ali Khan; Tahseenullah Khan; Muhammad Zafar (Environmental Monitoring and Assessment, 2021)

Metal accumulation potential, human health risks, and yield attributes of hundred bread wheat genotypes on irrigation with municipal and remediated wastewater - Said Akbar; Zeshan Ali; Sadam Hussain; Ashiq Mohammad; Yousaf Riaz; Adnan Shakeel; Ijaz Ahmad; Maria Mussarat; Riffat Naseem Malik; Kiran Yasmin Khan; Muhammad Sohail; Umar Masood Quraishi (Environmental Science and Pollution Research, 2021)

Carbon-Based Slow-Release Fertilizers for Efficient Nutrient Management: Synthesis, Applications, and Future Research Needs - Muhammad Rashid; Qaiser Hussain; Khalid Saifullah Khan; Mohammad I. Alwabel; Rifat Hayat; Muhammad Akmal; Shahzada Sohail Ijaz; Sarosh Alvi; Obaid-ur-Rehman (Journal of Soil Science and Plant Nutrition, 2021)

Renewable energy and non-renewable energy consumption: assessing the asymmetric role of monetary policy uncertainty in energy consumption - Muhammad Tayyab Sohail; Yu Xiuyuan; Ahmed Usman; Muhammad Tariq Majeed; Sana Ullah (Environmental Science and Pollution Research, 2021)

Green logistics, economic growth, and environmental quality: evidence from one belt and road initiative economies - Xiaolong Li; Sidra Sohail; Muhammad Tariq Majeed; Waheed Ahmad (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: The shadow economy in South Asia: dynamic effects on clean energy consumption and environmental pollution - Muhammad Tayyab Sohail; Sana Ullah; Muhammad Tariq Majeed; Ahmed Usman; Zubaria Andlib (Environmental Science and Pollution Research, 2021)
This study explores the symmetric and asymmetric effects of the shadow economy on clean energy and air pollution of South Asian countries over the period 1991–2019. The short-run ARDL findings for the clean energy model suggest that shadow economy increases clean energy consumption in Pakistan and Sri Lanka, whereas this effect is negative for India and insignificant for other countries. The long-run results indicate the adverse impact only for India and the effects of tax revenue on clean energy are positively significant in Sri Lanka while negatively signiicant in Nepal and Bangladesh. Institutional quality significantly increases clean energy in Pakistan, India, and Nepal. However, in the case of Pakistan and Nepal, institutional quality deteriorated the environmental quality. The results for the pollution model confer that shadow economy increases emissions in Pakistan, decreases in Bangladesh and Nepal, and has no effect in India and Sri Lanka. The nonlinear ARDL results reveal that the positive components of the shadow economy significantly increase clean energy consumption only in Pakistan; however, the negative components of the shadow economy are negatively significant in all countries except Sri Lanka and Nepal. However, the negative component of the informal sector of the economy reduces CO2 emissions in India and increases CO2 emissions in Bangladesh and Nepal. The results offer important policy implications for achieving clean energy and better environmental quality in South Asian countries.

Pakistan management of green transportation and environmental pollution: a nonlinear ARDL analysis - Muhammad Tayyab Sohail; Sana Ullah; Muhammad Tariq Majeed; Ahmed Usman (Environmental Science and Pollution Research, 2021)
Modern advances in nonlinear modeling have exposed that nonlinear models yield more robust results compared with linear models. Research on the effect of air-railway transportation on environmental pollution has now arrived into a new way of asymmetry analysis and captured the real issue among the nexus. This study aims to inspect the asymmetric impact of air-railway transportation on environmental pollution in Pakistan by using annual time series data from 1991 to 2019. The findings show that positive shock in air passenger carried and railway passenger carried increases carbon emissions, which implies that 1% increase in air passenger carried (railway passenger carried) enhances environmental pollution by 0.21% (0.32%) in long run in Pakistan. While positive shock in railway passengers carried increases environmental pollution and negative shock in railway passengers carried decreases the environmental pollution in the short run. The outcomes have also confirmed the short- and long-run asymmetries in Wald statistics. The findings are country-specific and it would be regionally specific.

Impact of light stimulation during incubation on hatching traits and post-hatch performance of commercial broilers - Muhammad Faisal Riaz; Athar Mahmud; Jibran Hussain; Abd ur Rehman; Muhammad Usman; Shahid Mehmood; Sohail Ahmad (Tropical Animal Health and Production, 2021)

Effects of soil application of two different fipronil formulations on some soil-dwelling non-target arthropods - Muhammad Asad; Sohail Ahmed; Rashad Rasool Khan; Abid Ali; Muhammad Fahad Raza; Ammarah Shabbir; Faisal Munir; Anam Noreen Abbas; Mubashir Tariq (International Journal of Tropical Insect Science, 2021)

Physicomechanical, stability, and pharmacokinetic evaluation of aceclofenac dimethyl urea cocrystals - Hafsa Afzal; Nasir Abbas; Amjad Hussain; Sumera Latif; Kanwal Fatima; Muhammad Sohail Arshad; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2021)

Elucidating Cd-mediated distinct rhizospheric and in planta ionomic and physio-biochemical responses of two contrasting Zea mays L. cultivars - Saghir Abbas; Muhammad Tariq Javed; Qasim Ali; Muhammad Sohail Akram; Kashif Tanwir; Shafaqat Ali; Hassan Javed Chaudhary; Naeem Iqbal (Physiology and Molecular Biology of Plants, 2021)

Research advances and applications of biosensing technology for the diagnosis of pathogens in sustainable agriculture - Qurban Ali; Sunny Ahmar; Muhammad Aamir Sohail; Muhammad Kamran; Mohsin Ali; Muhammad Hamzah Saleem; Muhammad Rizwan; Agha Mushtaque Ahmed; Freddy Mora-Poblete; Antônio Teixeira do Amaral Júnior; Mustansar Mubeen; Shafaqat Ali (Environmental Science and Pollution Research, 2021)

Nephroprotective effect of ethanol extract and fractions of a sea lettuce, Ulva fasciata against cisplatin-induced kidney injury in rats - Nida Sohail; Khan Hira; Junaid Ahmed Kori; Hafiza Farhat; Faizah Urooj; Waqas Khan; Viqar Sultana; Muhammad Shaiq Ali; Syed Ehteshamul-Haque (Environmental Science and Pollution Research, 2021)

Asymmetric effects of militarization on economic growth and environmental degradation: fresh evidence from Pakistan and India - Sana Ullah; Zubaria Andlib; Muhammad Tariq Majeed; Sidra Sohail; Muhammad Zubair Chishti (Environmental Science and Pollution Research, 2021)

Examining the asymmetric effects of Pakistan’s fiscal decentralization on economic growth and environmental quality - Xiaolong Li; Muhammad Zeeshan Younas; Zubaria Andlib; Sana Ullah; Sidra Sohail; Muhammad Hafeez (Environmental Science and Pollution Research, 2021)

Gas-mediated cancer therapy - Hang Zhang; Mengying Xie; Honghong Chen; Sneha Bavi; Muhammad Sohail; Rohit Bavi (Environmental Chemistry Letters, 2021)

Tectonic evolution, prospectivity and structural studies of the hanging wall of Main Boundary Thrust along Akhurwal-Kohat transect, Khyber Pakhtunkhwa: implications for future exploration - Muhammad Yaseen; Sohail Wahid; Sajjad Ahmad; Gohar Rehman; Jawad Ahmad; Muhammad Naveed Anjum; Mubashir Mehmood (Arabian Journal of Geosciences, 2021)

Soil nutrient status and crop productivity after 6 years of conservation tillage in a subtropical dryland - Sana ur Rehman; Shahzada Sohail Ijaz; Khalid Saifullah Khan; Muhammad Ansar; Qaiser Hussain (Arabian Journal of Geosciences, 2021)

Antibiofilm Effects of Macrolide Loaded Microneedle Patches: Prospects in Healing Infected Wounds - Muhammad Sohail Arshad; Aleema Tehreem Zahra; Saman Zafar; Hussain Zaman; Ambreen Akhtar; Muhammad Mazhar Ayaz; Israfil Kucuk; Mohammed Maniruzzaman; Ming-Wei Chang; Zeeshan Ahmad (Pharmaceutical Research, 2021)

Plant growth-promoting Bacillus sp. strain SDA-4 confers Cd tolerance by physio-biochemical improvements, better nutrient acquisition and diminished Cd uptake in Spinacia oleracea L. - Muhammad Shahid; Muhammad Tariq Javed; Kashif Tanwir; Muhammad Sohail Akram; Syeda Khola Tazeen; Muhammad Hamzah Saleem; Sajid Masood; Sadia Mujtaba; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2020)

Dechlorane Plus as an emerging environmental pollutant in Asia: a review - Mazhar Iqbal Zafar; Sundas Kali; Mehtabidah Ali; Muhammad Asam Riaz; Tayyaba Naz; Muhammad Mazhar Iqbal; Noshin Masood; Kashif Munawar; Bilal Jan; Sohail Ahmed; Amir Waseem; Muhammad Bilal Khan Niazi (Environmental Science and Pollution Research, 2020)

The role of financial development, tourism, and energy utilization in environmental deficit: evidence from 20 highest emitting economies - Muhammad Usman; Rakhshanda Kousar; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2020)

An empirical nexus between economic growth, energy utilization, trade policy, and ecological footprint: a continent-wise comparison in upper-middle-income countries - Muhammad Usman; Rakhshanda Kousar; Muhammad Rizwan Yaseen; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2020)

Enhanced uptake of Cd, Cr, and Cu in Catharanthus roseus (L.) G.Don by Bacillus cereus: application of moss and compost to reduce metal availability - Muhammad Umair Mushtaq; Ameena Iqbal; Ismat Nawaz; Cyrus Raza Mirza; Sohail Yousaf; Ghazanfar Farooq; Muhammad Arif Ali; Aqib Hassan Ali Khan; Mazhar Iqbal (Environmental Science and Pollution Research, 2020)

Sodium Exclusion Affects Seed Yield and Physiological Traits of Wheat Genotypes Grown Under Salt Stress - Muhammad Sohail Saddiq; Irfan Afzal; Shahzad M.A. Basra; Shahid Iqbal; Muhammad Ashraf (Journal of Soil Science and Plant Nutrition, 2020)

Environmental impacts and risk factors of renewable energy paradigm—a review - Muhammad Shahzad Nazir; Ziad M. Ali; Muhammad Bilal; Hafiz M. Sohail; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2020)

Evaluation of Factors Affecting Saccharification of Sugarcane Bagasse Using Cellulase Preparation from a Thermophilic Strain of Brevibacillus sp. - Maria Tariq Khan; Uroosa Ejaz; Muhammad Sohail (Current Microbiology, 2020)

Co-culturing corncob-immobilized yeasts on orange peels for the production of pectinase - Faizan Qadir; Uroosa Ejaz; Muhammad Sohail (Biotechnology Letters, 2020)

Enhancement of salt tolerance in maize (Zea mays L.) using locally isolated Bacillus sp. SR-2-1/1 - Khadija Rafiq; Muhammad Sohail Akram; Muhammad Shahid; Uzma Qaisar; Naeem Rashid (Biologia, 2020)

Induction of Modern Water Distribution Systems in Punjab of Indo-Pak Subcontinent, South Asia During Late Nineteenth Century by British Government - Muhammad Sohail; Suryyia Manzoor (Sustainable Water Resources Management, 2020)

Silybum marianum (milk thistle) improves vancomycin induced nephrotoxicity by downregulating apoptosis - Naila Malkani; Ammara Naeem; Farah Ijaz; Sidra Mumtaz; Saima Ashraf; Muhammad Imran Sohail (Molecular Biology Reports, 2020)

Influence of Pseudomonas japonica and organic amendments on the growth and metal tolerance of Celosia argentea L. - Ameena Iqbal; Muhammad Umair Mushtaq; Aqib Hassan Ali Khan; Ismat Nawaz; Sohail Yousaf; Zeshan; Mazhar Iqbal (Environmental Science and Pollution Research, 2020)

Inorganic fertilization improves quality and biomass of Moringa oleifera L. - Muhammad Farhan Aslam; Shahzad M. A. Basra; Muhammad Bilal Hafeez; Shahbaz Khan; Sohail Irshad; Shahid Iqbal; Muhammad Sohail Saqqid; Muhammad Zubair Akram (Agroforestry Systems, 2020)

Production analysis of broiler farming in central Punjab, Pakistan - Naeem Ur Rahman; Shahid Mehmood; Sohail Ahmad; Arshad Javid; Athar Mahmud; Jibran Hussain; Muhammad Shabir Shaheen; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2020)

Effect of biochars, biogenic, and inorganic amendments on dissolution and kinetic release of phytoavailable silicon in texturally different soils under submerged conditions - Muhammad Irfan Sohail; Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Ashar Ayub; Tariq Aziz; Muhammad Saqib; Ghulam Murtaza (Arabian Journal of Geosciences, 2020)

Environmental risk assessment of diclofenac residues in surface waters and wastewater: a hidden global threat to aquatic ecosystem - Hafsa Hanif; Amir Waseem; Sundas Kali; Naveeda Akhtar Qureshi; Muhammad Majid; Mazhar Iqbal; Tofeeq Ur-Rehman; Muhammad Tahir; Sohail Yousaf; Muhammad Mazhar Iqbal; Imtiaz Ahmad Khan; Mazhar Iqbal Zafar (Environmental Monitoring and Assessment, 2020)

5-Endo-dig cyclizations in organic syntheses - Muhammad Aamir Sajid; Zulfiqar Ali Khan; Sohail Anjum Shahzad; Syed Ali Raza Naqvi; Muhammad Usman (Molecular Diversity, 2020)

Fabrication and Characterization of Thiolated Chitosan Microneedle Patch for Transdermal Delivery of Tacrolimus - Zulcaif Ahmad; Muhammad Imran Khan; Muhammad Irfan Siddique; Hafiz Shoaib Sarwar; Gul Shahnaz; Syed Zajif Hussain; Nadeem Irfan Bukhari; Irshad Hussain; Muhammad Farhan Sohail (AAPS PharmSciTech, 2020)

Development and Characterization of Bioadhesive Film Embedded with Lignocaine and Calcium Fluoride Nanoparticles - Hira Ghafar; Muhammad Imran Khan; Hafiz Shoaib Sarwar; Samiya Yaqoob; Syed Zajif Hussain; Imran Tariq; Asad Ullah Madni; Gul Shahnaz; Muhammad Farhan Sohail (AAPS PharmSciTech, 2020)

Synergistic effect of heartwood extracts in combination with linseed oil as wood preservatives against subterranean termite Heterotermes indicola (Blattodea: Rhinotermitidae) - Babar Hassan; Sohail Ahmed; Grant Kirker; Mark E. Mankowski; Muhammad Misbah ul Haq (Environmental Science and Pollution Research, 2020)

Hydrological appraisal of rainfall estimates from radar, satellite, raingauge and satellite–gauge combination on the Qinhuai River Basin, China - Muhammad Ilyas Abro; Dehua Zhu; Ming Wei; Asghar Ali Majidano; Murad Ali Khaskheli; Zain Ul Abideen; Muhammad Sohail Memon (Hydrological Sciences Journal, 2019)

Improved transdermal delivery of cetirizine hydrochloride using polymeric microneedles - Muhammad Sohail Arshad; Sana Hassan; Amjad Hussain; Nasir Abbas; Israfil Kucuk; Kazem Nazari; Radeyah Ali; Suleman Ramzan; Ali Alqahtani; Eleftherios G. Andriotis; Dimitris G. Fatouros; Ming-Wei Chang; et al. (DARU Journal of Pharmaceutical Sciences, 2019)

Circulation of multiple subtypes (A, G and CRFs 02_AG) of human immunodeficiency virus type 1 (HIV-1) in selected districts of Punjab province, Pakistan - Saima Yaqub; Tahir Yaqub; Muhammad Zubair Shabbir; Asif Nadeem; Nadia Mukhtar; Firnas Ata Ur Rehman; Aziz-ul Rahman; Muhammad Furqan Shahid; Muzaffar Ali; Tayyebah Sohail; Zarfishan Tahir (Archives of Virology, 2019)

The effect of lead pollution on nutrient solution pH and concomitant changes in plant physiology of two contrasting Solanum melongena L. cultivars - Muhammad Tariq Javed; Noman Habib; Muhammad Sohail Akram; Qasim Ali; Muhammad Zulqurnain Haider; Kashif Tanwir; Asia Shauket; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2019)

Impact of insect growth regulators on biology and behavior of Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) - Mubasshir Sohail; Syed Saboor Khan; Raza Muhammad; Qadeer Ahmed Soomro; Muhammad Usman Asif; Bhai Khan Solangi (Ecotoxicology, 2019)

Metal-induced nephrotoxicity to diabetic and non-diabetic Wistar rats - Muhammad Ahsan Riaz; Zaib Un Nisa; Azra Mehmood; Muhammad Sohail Anjum; Khurram Shahzad (Environmental Science and Pollution Research, 2019)

Impact of biochar with different organic materials on carbon fractions, aggregate size distribution, and associated polysaccharides and soil moisture retention in an arid soil - Munir Abbas; Shahzada Sohail Ijaz; Muhammad Ansar; Qaiser Hussain; Asma Hassan; Muhammad Akmal; Muhammad Tahir; Muhammad Iqbal; Kashif Bashir; Sana-ur-Rehman (Arabian Journal of Geosciences, 2019)

Development and Evaluation of Optimized Thiolated Chitosan Proniosomal Gel Containing Duloxetine for Intranasal Delivery - Maryam khatoon; Muhammad Farhan Sohail; Gul Shahnaz; Fiza ur Rehman; Fakhar-ud-Din; Asim ur Rehman; Naseem Ullah; Umair Amin; Gul Majid Khan; Kifayat Ullah Shah (AAPS PharmSciTech, 2019)

Investigating the drinking and surface water quality and associated health risks in a semi-arid multi-industrial metropolis (Faisalabad), Pakistan - Yusra Mahfooz; Abdullah Yasar; Muhammad Tayyab Sohail; Amtul Bari Tabinda; Rizwan Rasheed; Samina Irshad; Balal Yousaf (Environmental Science and Pollution Research, 2019)

Technetium-99m labeled Ibuprofen: Development and biological evaluation using sterile inflammation induced animal models - Naeem-Ul-Haq Khan; Syed Ali Raza Naqvi; Hamza Sohail; Samina Roohi; Muhammad Asghar Jamal (Molecular Biology Reports, 2019)

Opportunities and challenges in the remediation of metal-contaminated soils by using tobacco (Nicotiana tabacum L.): a critical review - Muhammad Zia ur Rehman; Muhammad Rizwan; Muhammad Irfan Sohail; Shafaqat Ali; Aisha A. Waris; Hinnan Khalid; Asif Naeem; Hamaad Raza Ahmad; Arslan Rauf (Environmental Science and Pollution Research, 2019)

Comparative efficiency of peanut shell and peanut shell biochar for removal of arsenic from water - Muhammad Sohail Sattar; Muhammad Bilal Shakoor; Shafaqat Ali; Muhammad Rizwan; Nabeel Khan Niazi; Asim Jilani (Environmental Science and Pollution Research, 2019)

PEGylation: a promising strategy to overcome challenges to cancer-targeted nanomedicines: a review of challenges to clinical transition and promising resolution - Zahid Hussain; Shahzeb Khan; Muhammad Imran; Muhammad Sohail; Syed Wadood Ali Shah; Marcel de Matas (Drug Delivery and Translational Research, 2019)

RETRACTED ARTICLE: pH-responsive CAP-co-poly(methacrylic acid)-based hydrogel as an efficient platform for controlled gastrointestinal delivery: fabrication, characterization, in vitro and in vivo toxicity evaluation - Syed Ahmed Shah; Muhammad Sohail; Muhammad Usman Minhas; Nisar-ur-Rehman; Shahzeb Khan; Zahid Hussain; Mudassir; Arshad Mahmood; Mubeen Kousar; Asif Mahmood (Drug Delivery and Translational Research, 2019)

Natural and synthetic polymer-based smart biomaterials for management of ulcerative colitis: a review of recent developments and future prospects - Muhammad Sohail; Mudassir; Muhammad Usman Minhas; Shahzeb Khan; Zahid Hussain; Marcel de Matas; Syed Ahmed Shah; Samiullah Khan; Mubeen Kousar; Kaleem Ullah (Drug Delivery and Translational Research, 2019)

Enterobacter sp. strain Fs-11 adapted to diverse ecological conditions and promoted sunflower achene yield, nutrient uptake, and oil contents - Muhammad Shahid; Sohail Hameed; Mohsin Zafar; Muhammad Tahir; Muhammad Ijaz; Mohsin Tariq; Khadim Hussain; Amanat Ali (Brazilian Journal of Microbiology, 2019)

Integrated use of biochar and compost to improve soil microbial activity, nutrient availability, and plant growth in arid soil - Muhammad Akmal; Zubaira Maqbool; Khalid Saifullah Khan; Qaiser Hussain; Shahzada Sohail Ijaz; Muhammad Iqbal; Irfan Aziz; Amjad Hussain; Muhammad Subtain Abbas; Hafeez Ullah Rafa (Arabian Journal of Geosciences, 2019)

Interactive Effects of Genotype and Nitrogen on the Phenology and Yield Determination of Okra [Abelmoschus esculentus (L.)] - Saba Fatima; Muhammad Sohail Khan; Muhammad Nadeem; Ilham Khan; Kashif Waseem; Muhammad Nisar; Muhammad Iqbal (International Journal of Plant Production, 2019)

Domperidone nanocrystals with boosted oral bioavailability: fabrication, evaluation and molecular insight into the polymer-domperidone nanocrystal interaction - Stalielson Tatenda Ndlovu; Naseem Ullah; Shahzeb Khan; Pritika Ramharack; Mahmoud Soliman; Marcel de Matas; Muhammad Shahid; Muhammad Sohail; Muhammad Imran; Syed Wadood Ali Shah; Zahid Hussain (Drug Delivery and Translational Research, 2019)

Assessment of organochlorine pesticides in the Himalayan riverine ecosystems from Pakistan using passive sampling techniques - Rizwan Ullah; Rehana Asghar; Mujtaba Baqar; Adeel Mahmood; Syeda Nazish Ali; Muhammad Sohail; Ralf B. Schäfer; Syed Ali Musstjab Akber Shah Eqani (Environmental Science and Pollution Research, 2019)

Response of soil microbial biomass and enzymatic activity to biochar amendment in the organic carbon deficient arid soil: a 2-year field study - Muhammad Irfan; Qaiser Hussain; Khalid Saifullah Khan; Muhammad Akmal; Shahzada Sohail Ijaz; Rifat Hayat; Azeem Khalid; Muhammad Azeem; Muhammad Rashid (Arabian Journal of Geosciences, 2019)

Folate-Functionalized Thiomeric Nanoparticles for Enhanced Docetaxel Cytotoxicity and Improved Oral Bioavailability - Muhammad Sajjad; Muhammad Imran Khan; Sara Naveed; Sana Ijaz; Omer Salman Qureshi; Syed Atif Raza; Gul Shahnaz; Muhammad Farhan Sohail (AAPS PharmSciTech, 2019)

RETRACTED ARTICLE: Anthocyanins Improve Hippocampus-Dependent Memory Function and Prevent Neurodegeneration via JNK/Akt/GSK3β Signaling in LPS-Treated Adult Mice - Muhammad Sohail Khan; Tahir Ali; Min Woo Kim; Myeung Hoon Jo; Jong Il Chung; Myeong Ok Kim (Molecular Neurobiology, 2019)

Chemical investigations of Si-rich organic and inorganic amendments and correlation analysis between different chemical composition and Si contents in amendments - Muhammad Irfan Sohail; Muhammad Zia ur Rehman; Ghulam Murtaza; Muhammad Ashfaq Wahid (Arabian Journal of Geosciences, 2019)

Effect of biofertilizers and diatomaceous earth on life and movement of subterranean termites under laboratory conditions - Sohail Ahmed; Babar Hassan; Muhammad Umer Farooq (International Journal of Tropical Insect Science, 2018)

Cadmium (Cd) concentration in wheat (Triticum aestivum) grown in Cd-spiked soil varies with the doses and biochar feedstock - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Irfan Sohail; Amjad Hussain; Muhammad Farooq Qayyum; Hinnan Khalid; Muhammad Zeeshan; Naveeda Majid (Arabian Journal of Geosciences, 2018)

Coal mining trends, approaches, and safety hazards: a brief review - Muhammad Fahad Ullah; Abdullah M. Alamri; Khalid Mehmood; Mian Sohail Akram; Faisal Rehman; Saif Ur Rehman; Omar Riaz (Arabian Journal of Geosciences, 2018)

Recent developments in intelligent packaging for enhancing food quality and safety - Muhammad Sohail; Da-Wen Sun; Zhiwei Zhu (Critical Reviews in Food Science and Nutrition, 2018)

Simultaneously Improving Mechanical, Formulation, and In Vivo Performance of Naproxen by Co-Crystallization - Nasir Abbas; Sumera Latif; Hafsa Afzal; Muhammad Sohail Arshad; Amjad Hussain; Saleha Sadeeqa; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2018)

Preparation and Evaluation of Skin Wound Healing Chitosan-Based Hydrogel Membranes - Sarfaraz Ahmad; Muhammad Usman Minhas; Mahmood Ahmad; Muhammad Sohail; Orva Abdullah; Syed Faisal Badshah (AAPS PharmSciTech, 2018)

In vitro preconditioning of insulin-producing cells with growth factors improves their survival and ability to release insulin - Muhammad Sohail Anjum; Azra Mehmood; Faiza Mahmood; Muhammad Ali; Moazzam Nazir Tarrar; Shaheen N. Khan; Sheikh Riazuddin (Journal of Biosciences, 2018)

Potential Toxic Metal Accumulation in Soil, Forage and Blood Plasma of Buffaloes Sampled from Jhang, Pakistan - Zafar Iqbal Khan; Ilker Ugulu; Sara Umar; Kafeel Ahmad; Naunain Mehmood; Asma Ashfaq; Humayun Bashir; Muhammad Sohail (Bulletin of Environmental Contamination and Toxicology, 2018)

Genomic and biological characterization of Newcastle disease viruses isolated from migratory mallards (Anas platyrhynchos) - Momena Habib; Tahir Yaqub; Jawad Nazir; Wasim Shehzad; Aziz-ul-Rahman; Tayyebah Sohail; Nadia Mukhtar; Arsalan Mehboob; Muhammad Munir; Muhammad Zubair Shabbir (Archives of Virology, 2018)

Natural Dietary Supplementation of Anthocyanins via PI3K/Akt/Nrf2/HO-1 Pathways Mitigate Oxidative Stress, Neurodegeneration, and Memory Impairment in a Mouse Model of Alzheimer’s Disease - Tahir Ali; Taehyun Kim; Shafiq Ur Rehman; Muhammad Sohail Khan; Faiz Ul Amin; Mehtab Khan; Muhammad Ikram; Myeong Ok Kim (Molecular Neurobiology, 2018)

Metal accumulation in Raphanus sativus and Brassica rapa: an assessment of potential health risk for inhabitants in Punjab, Pakistan - Kafeel Ahmad; Asma Ashfaq; Zafar Iqbal Khan; Humayun Bashir; Muhammad Sohail; Naunain Mehmood; Yunus Dogan (Environmental Science and Pollution Research, 2018)

RETRACTED ARTICLE: Evaluating toxicity of copper(II) oxide nanoparticles (CuO-NPs) through waterborne exposure to tilapia (Oreochromis mossambicus) by tissue accumulation, oxidative stress, histopathology, and genotoxicity - Khurram Shahzad; Muhammad Naeem Khan; Farhat Jabeen; Nasreen Kosour; Abdul Shakoor Chaudhry; Muhammad Sohail (Environmental Science and Pollution Research, 2018)

Impact of city effluents on water quality of Indus River: assessment of temporal and spatial variations in the southern region of Khyber Pakhtunkhwa, Pakistan - Ilham Khan; Azim Khan; Muhammad Sohail Khan; Shabnam Zafar; Asma Hameed; Shakeel Badshah; Shafiq Ur Rehman; Hidayat Ullah; Ghazala Yasmeen (Environmental Monitoring and Assessment, 2018)

Sugarcane bagasse-derived biochar reduces the cadmium and chromium bioavailability to mash bean and enhances the microbial activity in contaminated soil - Saqib Bashir; Qaiser Hussain; Muhammad Akmal; Muhammad Riaz; Hongqing Hu; Shahzada Sohail Ijaz; Muhammad Iqbal; Shaukat Abro; Sajid Mehmood; Munir Ahmad (Journal of Soils and Sediments, 2018)

Application of gravity and magnetic methods for the crustal study and delineating associated ores in the western limb of Hazara Kashmir Syntaxis, Northwest Himalayas, Pakistan - Muhammad Rustam Khan; Shahid Saleem Bilali; Fahad Hameed; Awais Rabnawaz; Sohail Mustafa; Naveed Azad; Muhammad Basharat; Abrar Niaz (Arabian Journal of Geosciences, 2018)

Evolutionary significance of selected EDAR variants in Tibetan high-altitude adaptations - Jianming Shao; Muhammad Sohail Raza; Basang Zhuoma; Changqing Zeng (Science China Life Sciences, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Deciphering the growth, organic acid exudations, and ionic homeostasis of Amaranthus viridis L. and Portulaca oleracea L. under lead chloride stress - Muhammad Tariq Javed; Muhammad Sohail Akram; Noman Habib; Kashif Tanwir; Qasim Ali; Nabeel Khan Niazi; Huma Gul; Naeem Iqbal (Environmental Science and Pollution Research, 2018)

Regenerative Potential of Platelet Rich Fibrin (PRF) for Curing Intrabony Periodontal Defects: A Systematic Review of Clinical Studies - Shariq Najeeb; Zohaib Khurshid; Muhammad Atif Saleem Agwan; Shazia Akhbar Ansari; Muhammad Sohail Zafar; Jukka Pekka Matinlinna (Tissue Engineering and Regenerative Medicine, 2017)

A measles outbreak in Sindh, Pakistan caused by a genotype B3 virus - Syed Sohail Zahoor Zaidi; Abdul Hameed; Naeem Ali; Massab Umair; Muhammad Masroor Alam; Muhammad Suleman Rana; Salmaan Sharif; Uzma Bashir Aamir; Shahzad Shaukat; Mehar Angez; Adnan Khurshid; Ribqa Akhtar; et al. (Archives of Virology, 2017)

Rice bran nutraceutics: A comprehensive review - Muhammad Sohail; Allah Rakha; Masood Sadiq Butt; Muhammad Jawad Iqbal; Summer Rashid (Critical Reviews in Food Science and Nutrition, 2017)

From REDD+ MRV Perspective: Comparison of Two Different Forest Management Regimes Using Geospatial Techniques in Ludi Khola Watershed, Gorkha District, Nepal - Hammad Gilani; Muhammad Sohail; Upama Ashish Koju (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Contrasting Effects of Organic and Inorganic Amendments on Reducing Lead Toxicity in Wheat - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Sabir; Muhammad I. Sohail (Bulletin of Environmental Contamination and Toxicology, 2017)

Using geographical information systems to assess groundwater contamination from arsenic and related diseases based on survey data in Lahore, Pakistan - Muhammad Imran; Sohail Jahanzaib; Ather Ashraf (Arabian Journal of Geosciences, 2017)

Postpartum endocrine activities, metabolic attributes and milk yield are influenced by thermal stress in crossbred dairy cows - Ihsanullah; Muhammad Subhan Qureshi; Syed Muhammad Suhail; Sohail Akhtar; Rifat Ullah Khan (International Journal of Biometeorology, 2017)

Identification of a novel copper-activated and halide-tolerant laccase in Geobacillus thermopakistaniensis - Saadia Basheer; Naeem Rashid; Raza Ashraf; Muhammad Sohail Akram; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Assessing impact of effluent discharge on irrigation water quality in southern region of Khyber Pakhtunkhwa, Pakistan - Shabnam Zafar; Azim Khan; Hidayat Ullah; Muhammad Sohail Khan; Ilham Khan; Asma Hameed; Shafeeq Ur Rehman; Ghazala Yasmeen (Environmental Monitoring and Assessment, 2017)

Process Understanding in Freeze-Drying Cycle Development: Applications for Through-Vial Impedance Spectroscopy (TVIS) in Mini-pilot Studies - Geoff Smith; Muhammad Sohail Arshad; Eugene Polygalov; Irina Ermolina; Timothy R McCoy; Paul Matejtschuk (Journal of Pharmaceutical Innovation, 2017)

Exogenous triacontanol-mediated increase in phenolics, proline, activity of nitrate reductase, and shoot k+ confers salt tolerance in maize (Zea mays L.) - Shagufta Perveen; Muhammad Iqbal; Abida Parveen; Muhammad Sohail Akram; Muhammad Shahbaz; Shehnal Akber; Aneeqa Mehboob (Brazilian Journal of Botany, 2017)

Respiratory syncytial virus and influenza are the key viral pathogens in children <2 years hospitalized with bronchiolitis and pneumonia in Islamabad Pakistan - Uzma Bashir; Nadia Nisar; Yasir Arshad; Muhammad Masroor Alam; Asiya Ashraf; Hajra Sadia; Birjees Mazher Kazi; Syed Sohail Zahoor Zaidi (Archives of Virology, 2017)

Health risk assessment of heavy metals in wheat using different water qualities: implication for human health - Zafar Iqbal Khan; Kafeel Ahmad; Sidrah Rehman; Samra Siddique; Humayun Bashir; Asma Zafar; Muhammad Sohail; Salem Alhajj Ali; Eugenio Cazzato; Giuseppe De Mastro (Environmental Science and Pollution Research, 2017)

Ailanthus altissima (Miller) Swingle fruit - new acyl β -sitosteryl glucoside and in vitro pharmacological evaluation - Sohail Khan; Aftab Hussain; Ansar Mehmood; Rashad Mehmood; Shagufta Perveen; Muhammad Imran (Natural Product Research, 2016)

Bioaccumulation of heavy metals and analysis of mineral element alongside proximate composition in foot, gills and mantle of freshwater mussels (Anodonta anatina) - Muhammad Sohail; Muhammad Naeem Khan; Abdul Shakoor Chaudhry; Naureen Aziz Qureshi (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Tectonic study of the Sub-Himalayas based on geophysical data in Azad Jammu and Kashmir and northern Pakistan - Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Muhammad Basharat; Sohail Mustafa (Journal of Earth Science, 2016)

Petrology and geochemistry of Jura granite and granite gneiss in the Neelum Valley, Lesser Himalayas (Kashmir, Pakistan) - Muhammad Saleem Mughal; Muhammad Sabir Khan; Muhammad Rustam Khan; Sohail Mustafa; Fahad Hameed; Muhammad Basharat; Abrar Niaz (Arabian Journal of Geosciences, 2016)

Beta-haemolytic streptococcal endocarditis: clinical presentation, management and outcomes - Abdelghani El Rafei; Daniel C. DeSimone; Christopher V. DeSimone; Brian D. Lahr; James M. Steckelberg; Muhammad R. Sohail; Walter R. Wilson; Larry M. Baddour (Infectious Diseases, 2016)

Evaluation of source rocks using one dimensional maturity modeling in Lower Indus Basin, Pakistan - Faisal Qayyum; Muhammad Hanif; Muhammad Mujtaba; Sohail Wahid; Fahad Ali (Arabian Journal of Geosciences, 2016)

Oral tissue engineering progress and challenges - Muhammad Sohail Zafar; Zohaib Khurshid; Khalid Almas (Tissue Engineering and Regenerative Medicine, 2015)

Diazoxide preconditioning of endothelial progenitor cells from streptozotocin-induced type 1 diabetic rats improves their ability to repair diabetic cardiomyopathy - Muhammad Ali; Azra Mehmood; Muhammad Sohail Anjum; Moazzam Nazir Tarrar; Shaheen N. Khan; Sheikh Riazuddin (Molecular and Cellular Biochemistry, 2015)

Effect of Beauveria bassiana infection on the feeding performance and antioxidant defence of red palm weevil, Rhynchophorus ferrugineus - Abid Hussain; Muhammad Rizwan-ul-Haq; Hassan Al-Ayedh; Sohail Ahmed; Ahmed Mohammed Al-Jabr (BioControl, 2015)

Geotechnical study of marble, schist, and granite as dimension stone: a case study from parts of Lesser Himalaya, Neelum Valley Area, Azad Kashmir, Pakistan - Sohail Mustafa; Muhammad Arshad Khan; Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Aamir Asghar; Abrar Niaz (Bulletin of Engineering Geology and the Environment, 2015)

Efficacy of silicon priming and fertigation to modulate seedling’s vigor and ion homeostasis of wheat (Triticum aestivum L.) under saline environment - Muhammad Azeem; Naeem Iqbal; Shakila Kausar; M. Tariq Javed; M. Sohail Akram; M. Asim Sajid (Environmental Science and Pollution Research, 2015)

Seasonal abundance of soil arthropods in relation to meteorological and edaphic factors in the agroecosystems of Faisalabad, Punjab, Pakistan - Muhammad Mussadiq Shakir; Sohail Ahmed (International Journal of Biometeorology, 2015)

Piercing and incubation method of in planta transformation producing stable transgenic plants by overexpressing DREB1A gene in tomato (Solanum lycopersicum Mill.) - Sabir Hussain Shah; Shaukat Ali; Sohail Ahmad Jan; Jalal-Ud-Din; Ghulam Muhammad Ali (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Monitoring impacts of air pollution: PIXE analysis and histopathological modalities in evaluating relative risks of elemental contamination - Sohail Ejaz; Gerry Amor Camer; Khaleeq Anwar; Muhammad Ashraf (Ecotoxicology, 2014)

Factors Affecting the Use of Impedance Spectroscopy in the Characterisation of the Freezing Stage of the Lyophilisation Process: the Impact of Liquid Fill Height in Relation to Electrode Geometry - Geoff Smith; Muhammad Sohail Arshad; Eugene Polygalov; Irina Ermolina (AAPS PharmSciTech, 2014)

MRI and neuropathological validations of the involvement of air pollutants in cortical selective neuronal loss - Sohail Ejaz; Khaleeq Anwar; Muhammad Ashraf (Environmental Science and Pollution Research, 2014)

The endophyte Enterobacter sp. FD17: a maize growth enhancer selected based on rigorous testing of plant beneficial traits and colonization characteristics - Muhammad Naveed; Birgit Mitter; Sohail Yousaf; Milica Pastar; Muhammad Afzal; Angela Sessitsch (Biology and Fertility of Soils, 2014)

Synthesis of chemically cross-linked polyvinyl alcohol-co-poly (methacrylic acid) hydrogels by copolymerization; a potential graft-polymeric carrier for oral delivery of 5-fluorouracil - Muhammad Usman Minhas; Mahmood Ahmad; Liaqat Ali; Muhammad Sohail (DARU Journal of Pharmaceutical Sciences, 2013)
Background of the Study The propose of the present work was to develop chemically cross-linked polyvinyl alcohol-co-poly(methacrylic acid) hydrogel (PVA-MAA hydrogel) for pH responsive delivery of 5-Fluorouracil (5-FU). Methods PVA based hydrogels were prepared by free radical copolymerization. PVA has been cross-linked chemically with monomer (methacrylic acid) in aqueous medium, cross-linking agent was ethylene glycol di-methacrylate (EGDMA) and benzoyl peroxide was added as reaction initiator. 5-FU was loaded as model drug. FTIR, XRD, TGA and DSC were performed for characterization of copolymer. Surface morphology was studied by SEM. pH sensitive properties were evaluated by swelling dynamics and equilibrium swelling ratio at low and higher pH. Results FTIR, XRD, TGA and DSC studies confirmed the formation of new copolymer. Formulations with higher MAA contents showed maximum swelling at 7.4 pH. High drug loading and higher drug release has been observed at pH 7.4. Conclusions The current study concludes that a stable copolymeric network of PVA was developed with MAA. The prepared hydrogels were highly pH responsive. This polymeric network could be a potential delivery system for colon targeting of 5-FU in colorectal cancers.

Cytotoxic, phytotoxic, and mutagenic appraisal to ascertain toxicological potential of particulate matter emitted from automobiles - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Imran Altaf; Aftab Ahmad Anjum (Environmental Science and Pollution Research, 2013)

Monitoring trace elements generated by automobiles: air pollutants with possible health impacts - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2013)

Model-Based Evaluation of Maturity Type of Potato Using a Diverse Set of Standard Cultivars and a Segregating Diploid Population - Muhammad Sohail Khan; Herman J. van Eck; Paul C. Struik (Potato Research, 2013)

Molecular characterization of a new synthetic cry2ab gene in Nicotiana tabacum - Sohail Mehmood Karimi; Muhammad Nouman Sohail; Imran Amin; Shahid Mansoor; Zahid Mukhtar (Biotechnology Letters, 2013)

Effects of interactions among Metarhizium anisopliae, Bacillus thuringiensis and chlorantraniliprole on the mortality and pupation of six geographically distinct Helicoverpa armigera field populations - Waqas Wakil; M. Usman Ghazanfar; Tahira Riasat; Mirza Abdul Qayyum; Sohail Ahmed; Muhammad Yasin (Phytoparasitica, 2013)

Genetic analysis of Newcastle disease virus from Punjab, Pakistan - Muhammad Zubair Shabbir; Muhammad Abbas; Tahir Yaqub; Nadia Mukhtar; Atta Subhani; Hasham Habib; Muhammad Umar Sohail; Muhammad Munir (Virus Genes, 2013)

Letter to the Editor: Cotton leaf curl Multan betasatellite strains cloned from Gossypium barbadense further supports selection due to host resistance - Muhammad Tehseen Azhar; Sohail Akhtar; Shahid Mansoor (Virus Genes, 2012)

Root colonization and growth promotion of sunflower (Helianthus annuus L.) by phosphate solubilizing Enterobacter sp. Fs-11 - Muhammad Shahid; Sohail Hameed; Asma Imran; Saira Ali; Jan Dirk van Elsas (World Journal of Microbiology and Biotechnology, 2012)

Development of broad-spectrum insect-resistant tobacco by expression of synthetic cry1Ac and cry2Ab genes - Muhammad Nouman Sohail; Sohail Mehmood Karimi; Shaheen Asad; Shahid Mansoor; Yusuf Zafar; Zahid Mukhtar (Biotechnology Letters, 2012)

Characterization of tannery effluent wastewater by proton-induced X-ray emission (PIXE) analysis to investigate their role in water pollution - Lubna Shakir; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2012)

Fat-tailed sheep production systems in the Khyber Pakhtunkhwa Province of Pakistan - Muhammad Ibrahim; Sohail Ahmad; Zahoor Ahmad Swati; Ghufran Ullah (Tropical Animal Health and Production, 2011)

Nutrients intake, digestibility, nitrogen balance and growth performance of sheep fed different silages with or without concentrate - Sohail H. Khan; Muhammad Aasif Shahzad; Mahr Nisa; Muhammad Sarwar (Tropical Animal Health and Production, 2011)

Multiple metal tolerance and biosorption of cadmium by Candida tropicalis isolated from industrial effluents: glutathione as detoxifying agent - Abdul Rehman; Muhammad Sohail Anjum (Environmental Monitoring and Assessment, 2011)

Cytology of infection of Fusarium mangiferae Britz in different malformed reproductive parts of mango - Zafar Iqbal; Sohail Hameed; Muhammad Akbar Anjum; Altaf Ahmad Dasti; Ahmad Saleem (European Journal of Plant Pathology, 2010)

Cadmium Uptake by Yeast, Candida tropicalis, Isolated from Industrial Effluents and Its Potential Use in Wastewater Clean-Up Operations - Abdul Rehman; Muhammad Sohail Anjum (Water, Air, & Soil Pollution, 2010)